Resin composition
Patent Information
- Application Number
- JP2024220115
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0008】 本発明によれば、耐衝撃性に優れる絶縁層を形成可能な樹脂組成物;その樹脂組成物の硬化物;その樹脂組成物を含有するシート状積層材料;その樹脂組成物で形成される樹脂組成物層を有する樹脂シート;その樹脂組成物の硬化物を含む絶縁層を備えるプリント配線板;並びに、そのプリント配線板を備える半導体装置;を提供できる。
Smart Images

Figure 2025028240000013 
Figure 2025028240000001 
Figure 2025028240000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. [Background technology]
[0002] A known manufacturing technique for printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked. In the build-up method, the insulating layers are generally formed from a cured product obtained by curing a resin composition (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-23714 A Summary of the Invention [Problem to be solved by the invention]
[0004] Semiconductor devices on which printed wiring boards are provided include mobile devices such as smartphones. These mobile devices are often subjected to impacts. For example, mobile devices may be accidentally dropped during use, and thus may be subjected to impacts due to the drop. When subjected to impacts, the insulating layer and the conductive layer in the printed wiring board may peel off, or cracks may form in the insulating layer. Therefore, there is a demand for the development of a resin composition capable of forming an insulating layer with excellent impact resistance.
[0005] The present invention has been devised in view of the above-mentioned problems, and has an object to provide a resin composition capable of forming an insulating layer having excellent impact resistance; a cured product of the resin composition; a sheet-like laminate material containing the resin composition; a resin sheet having a resin composition layer formed from the resin composition; a printed wiring board including an insulating layer including a cured product of the resin composition; and a semiconductor device including the printed wiring board. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by appropriately adjusting the composition of a resin composition containing (A) a curable resin and (B) an inorganic filler, thereby completing the present invention. That is, the present invention includes the following.
[0007] [1] A resin composition comprising (A) a curable resin and (B) an inorganic filler, The specific gravity of the cured product obtained by curing the resin composition is 1.6 g / cm 3 is as follows: A resin composition, wherein a cured product obtained by curing the resin composition has a thermal expansion coefficient of 40 ppm / °C or less. [2] The resin composition according to [1], wherein the inorganic filler (B) has an average particle size of 0.01 μm or more and 5 μm or less. [3] (B) The BET specific surface area of the inorganic filler is 1 m 2 / g or more, 100m 2 / g or less. [4] The resin composition according to any one of [1] to [3], wherein the inorganic filler (B) includes a hollow inorganic filler (B-1) having voids therein. [5] The resin composition according to [4], wherein the hollow inorganic filler (B-1) has a porosity of 10 volume % or more. [6] The resin composition according to any one of [1] to [5], further comprising (C) organic particles. [7] The resin composition according to [6], wherein the amount of the organic particles (C) is 2% by mass or more based on 100% by mass of the nonvolatile components of the resin composition. [8] (C) An organic particle having a shell portion and a built-in portion formed within the shell portion, The resin composition according to [6] or [7], wherein the built-in portion contains a rubber component or is a hollow portion. [9] The resin composition according to any one of [1] to [8], wherein the curable resin (A) is selected from the group consisting of thermosetting resins and photocurable resins.
[10] The resin composition according to [9], wherein the thermosetting resin comprises at least one resin selected from the group consisting of an epoxy resin, a phenolic resin, an active ester resin, a cyanate resin, and a radical polymerizable resin.
[11] The resin composition according to [9] or
[10] , wherein the photocurable resin contains a radical polymerizable resin.
[12] A resin composition comprising (A) a curable resin, (B) an inorganic filler, and (C) organic particles, (B) The inorganic filler contains (B-1) a hollow inorganic filler having pores therein, (B-1) The hollow inorganic filler has a porosity of 10% by volume or more, The amount of the inorganic filler (B) is 40% by volume or more relative to 100% by volume of the nonvolatile components of the resin composition; A resin composition, wherein the amount of the hollow inorganic filler (B-1) is 10% by volume or more relative to 100% by volume of the nonvolatile components of the resin composition.
[13] The resin composition according to any one of [1] to
[12] , which is for forming an insulating layer.
[14] A cured product of the resin composition according to any one of [1] to
[13] .
[15] A sheet-like laminate material containing the resin composition according to any one of [1] to
[13] .
[16] A resin sheet comprising a support and a resin composition layer formed on the support from the resin composition according to any one of [1] to
[13] .
[17] A printed wiring board having an insulating layer containing a cured product of the resin composition according to any one of [1] to
[13] .
[18] A semiconductor device comprising the printed wiring board according to
[17] . Effect of the Invention
[0008] According to the present invention, there can be provided a resin composition capable of forming an insulating layer having excellent impact resistance; a cured product of the resin composition; a sheet-like laminate material containing the resin composition; a resin sheet having a resin composition layer formed from the resin composition; a printed wiring board comprising an insulating layer including a cured product of the resin composition; and a semiconductor device comprising the printed wiring board. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a front view that shows a schematic view of a drop test carried out for evaluating impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims and their equivalents.
[0011] In the following description, the term "(meth)acrylic" includes acrylic, methacrylic, and combinations thereof. The term "(meth)acrylate" includes acrylate, methacrylate, and combinations thereof. The term "(meth)acrylonitrile" includes acrylonitrile, methacrylonitrile, and combinations thereof.
[0012] [1. Overview of resin composition according to the first embodiment] The resin composition according to the first embodiment of the present invention contains a combination of (A) a curable resin and (B) an inorganic filler. The cured product obtained by curing this resin composition has a specific gravity in a specific range. The cured product obtained by curing this resin composition has a thermal expansion coefficient in a specific range. According to a resin composition that satisfies such requirements, an insulating layer having excellent impact resistance can be formed. Therefore, an insulating layer including a cured product of the resin composition according to the first embodiment of the present invention can suppress peeling between the insulating layer and the conductive layer when an impact is applied, and can suppress the formation of cracks in the insulating layer. In the following description, the property of suppressing peeling between the insulating layer and the conductive layer when an impact is applied is sometimes referred to as "impact peel resistance", and the property of suppressing cracks when an impact is applied is sometimes referred to as "impact crack resistance".
[0013] The resin composition according to the first embodiment of the present invention preferably contains (C) organic particles in combination with (A) the curable resin and (B) the inorganic filler. The resin composition according to the first embodiment of the present invention may further contain any optional component.
[0014] The present inventors speculate that the mechanism by which the resin composition according to the first embodiment of the present invention provides the above-mentioned excellent impact resistance is as follows, however, the technical scope of the present invention is not limited by the mechanism described below.
[0015] In general, the thermal expansion coefficient of the curable resin (A) is large, and the thermal expansion coefficient of the inorganic filler (B) is small. Therefore, in order to obtain a cured product having a thermal expansion coefficient in a specific small range, the resin composition is required to contain a large amount of the inorganic filler (B). Therefore, if the cured product of the resin composition has a thermal expansion coefficient in a specific small range, it indicates that the amount of the inorganic filler (B) contained in the resin composition is large. In this way, when the amount of the inorganic filler (B) is large, the inorganic filler (B) functions as an aggregate in the cured product, and the rigidity of the cured product can be increased. And, the high rigidity of the cured product can increase the impact resistance of the cured product.
[0016] In addition, since the specific gravity of an inorganic material is generally greater than that of a resin, the specific gravity of the cured product tends to increase when the amount of inorganic filler is increased. Therefore, in the resin composition according to the first embodiment of the present invention, the type and amount of (B) inorganic filler are controlled in order to keep the specific gravity of the cured product within a specific small range while using a large amount of (B) inorganic filler. For example, by using an appropriate amount of (B-1) hollow inorganic filler having voids inside, the cured product can have a specific small range of specific gravity. In general, the cured product of a conventional resin composition containing a curable resin and an inorganic filler has a tendency to become more brittle when the amount of inorganic filler is large. In contrast, if the specific gravity of the cured product is set within a specific small range by devising the (B) inorganic filler, it is surprisingly possible to suppress the brittleness of the cured product and increase its resistance to impact. According to the study by the present inventors, it is considered that, particularly when (B) inorganic filler contains (B-1) hollow inorganic filler, the voids in (B-1) hollow inorganic filler mitigate the energy of the impact, improving the impact resistance. Furthermore, when the resin composition contains (C) organic particles, it is believed that the action of the (C) organic particles also synergistically mitigates the impact energy, thereby achieving an effective improvement in impact resistance.
[0017] [2.(A) Curing resin] The resin composition according to the first embodiment of the present invention contains a curable resin (A) as the component (A). The curable resin (A) may be selected from the group consisting of a thermosetting resin and a photocurable resin. Thus, as the curable resin (A), only a thermosetting resin may be used, only a photocurable resin may be used, or a combination of a thermosetting resin and a photocurable resin may be used. Moreover, the curable resin may be used alone or in combination of two or more types.
[0018] As the thermosetting resin, a resin that can be cured when heat is applied can be used. Examples of the thermosetting resin include epoxy resin, phenol resin, active ester resin, cyanate resin, carbodiimide resin, acid anhydride resin, amine resin, benzoxazine resin, thiol resin, and radical polymerizable resin. The thermosetting resin may be used alone or in combination of two or more. Among them, the thermosetting resin preferably includes at least one selected from the group consisting of epoxy resin, phenol resin, active ester resin, cyanate resin, and radical polymerizable resin.
[0019] In particular, from the viewpoint of obtaining the effects of the present invention significantly, it is preferable to use a combination of an epoxy resin and a resin capable of reacting with the epoxy resin to cure the resin composition. The resin capable of reacting with the epoxy resin to cure the resin composition may be referred to as a "curing agent" hereinafter. Examples of the curing agent include phenolic resin, active ester resin, cyanate resin, carbodiimide resin, acid anhydride resin, amine resin, benzoxazine resin, and thiol resin. Among them, phenolic resin, active ester resin, cyanate resin, and carbodiimide resin are preferred, and phenolic resin, active ester resin, and cyanate resin are more preferred. In addition, the curing agent may be used alone or in combination of two or more types.
[0020] The epoxy resin is a curable resin having an epoxy group. Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, and phenolphthalimidine type epoxy resins. The epoxy resin may be used alone or in combination of two or more kinds.
[0021] From the viewpoint of obtaining a cured product having excellent heat resistance, the epoxy resin preferably contains an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles. Examples of epoxy resins containing an aromatic structure include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, bisxylenol type epoxy resins, glycidylamine type epoxy resins having an aromatic structure, glycidyl ester type epoxy resins having an aromatic structure, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins having an aromatic structure, epoxy resins having a butadiene structure having an aromatic structure, alicyclic epoxy resins having an aromatic structure, heterocyclic epoxy resins, spiro ring-containing epoxy resins having an aromatic structure, cyclohexane dimethanol type epoxy resins having an aromatic structure, naphthylene ether type epoxy resins, trimethylol type epoxy resins having an aromatic structure, and tetraphenylethane type epoxy resins having an aromatic structure.
[0022] The (A) curable resin preferably contains, as an epoxy resin, an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0023] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only liquid epoxy resins as the epoxy resin, or may contain only solid epoxy resins, or may contain a combination of liquid epoxy resins and solid epoxy resins.
[0024] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0025] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred.
[0026] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" ( glycidylamine type epoxy resin); ADEKA's "EP-4088S" (dicyclopentadiene type epoxy resin); Nippon Steel Chemical & Material Chemical's "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); Nagase Chemtex's "EX-721" (glycidyl ester type epoxy resin); Daicel's "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton); Daicel's "PB-3600", Nippon Soda's "JP-100" and "JP-200" (epoxy resin having a butadiene structure); Nippon Steel Chemical & Material's "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin), etc. These may be used alone or in combination of two or more types.
[0027] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0028] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.
[0029] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-7311" manufactured by DIC Corporation. , "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V", "ESN4 100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "Y Examples of epoxy resins include "X7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YX7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.
[0030] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably 20:1 to 1:20, more preferably 10:1 to 1:10, and particularly preferably 7:1 to 1:7.
[0031] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 3,000 g / eq., further preferably 80 g / eq. to 2,000 g / eq., and particularly preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent represents the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0032] The weight average molecular weight (Mw) of the epoxy resin is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0033] The amount of the epoxy resin in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 5% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 35% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the amount of the epoxy resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0034] The amount of epoxy resin in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, particularly preferably 65% by mass or less, when the resin component in the resin composition is taken as 100% by mass. The resin component of the resin composition refers to the non-volatile components of the resin composition excluding the (B) inorganic filler, unless otherwise specified. When the amount of epoxy resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0035] As the phenolic resin, a compound having one or more, preferably two or more, hydroxyl groups bonded to an aromatic ring such as a benzene ring or a naphthalene ring in one molecule can be used. When combined with an epoxy resin, the phenolic resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called a "phenolic hardener." From the viewpoint of heat resistance and water resistance, a phenolic resin having a novolac structure is preferred. From the viewpoint of adhesion, a nitrogen-containing phenolic resin is preferred, and a triazine skeleton-containing phenolic resin is more preferred. Among these, a triazine skeleton-containing phenolic novolac resin is preferred from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion. Specific examples of phenolic resins include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.
[0036] As the active ester resin, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferably used. When combined with an epoxy resin, the active ester resin can react with the epoxy resin to harden the resin composition, and is therefore sometimes called an "active ester-based curing agent." The active ester resin is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0037] Specifically, the active ester resin is preferably a dicyclopentadiene type active ester resin, a naphthalene type active ester resin containing a naphthalene structure, an active ester resin containing an acetylated product of phenol novolac, or an active ester resin containing a benzoylated product of phenol novolac, and more preferably at least one selected from a dicyclopentadiene type active ester resin and a naphthalene type active ester resin. As the dicyclopentadiene type active ester resin, an active ester resin containing a dicyclopentadiene type diphenol structure is preferable.
[0038] Commercially available active ester resins include, for example, active ester resins containing a dicyclopentadiene-type diphenol structure such as "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester resins containing a naphthalene structure such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-8150-60T", and "EXB-815 Examples of such active ester resins include "EXB9401" (manufactured by DIC Corporation), an active ester resin which is an acetylated product of phenol novolac, such as "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester resin which is a benzoylated product of phenol novolac, such as "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester resin which contains a styryl group and a naphthalene structure, such as "PC1300-02-65MA" (manufactured by Air Water Corporation).
[0039] As the cyanate resin, a compound having one or more, preferably two or more, cyanate groups in one molecule can be used. When combined with an epoxy resin, the cyanate resin reacts with the epoxy resin to harden the resin composition, and therefore is sometimes called a "cyanate-based curing agent." Examples of the cyanate resin include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl)thioether, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate resins include "PT30" and "PT60" (both of which are phenol novolac type multifunctional cyanate resins) manufactured by Lonza Japan, "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted into triazine to form a trimer).
[0040] As the carbodiimide resin, a compound having one or more, preferably two or more, carbodiimide structures in one molecule can be used. When combined with an epoxy resin, the carbodiimide resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called a "carbodiimide-based hardener." Specific examples of the carbodiimide resin include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); poly(phenylenecarbodiimide), poly(naphthalenecarbodiimide), and the like. Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(methylenediphenylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide]. Commercially available carbodiimide resins include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07" and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400" and "Hi-Kasil 510" manufactured by Rhein Chemie.
[0041] As the acid anhydride resin, a compound having one or more, preferably two or more, acid anhydride groups in one molecule can be used. When combined with an epoxy resin, the acid anhydride resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called an "acid anhydride-based curing agent." Specific examples of the acid anhydride resin include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, and the like. Examples of such anhydrides include water, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride resins include, for example, "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd.; "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.; and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley Corporation.
[0042] As the amine resin, a compound having one or more, preferably two or more, amino groups in one molecule can be used. When combined with an epoxy resin, the amine resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called an "amine-based hardener." Examples of the amine resin include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines, and among these, aromatic amines are preferred. The amine resin is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine resins include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propionate. Pan, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. Commercially available amine resins include, for example, "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd.; "Epicure W" manufactured by Mitsubishi Chemical Corporation; and "DTDA" manufactured by Sumitomo Seika Chemicals Co., Ltd.
[0043] Benzoxazine resins, when combined with epoxy resins, can react with the epoxy resin to harden the resin composition, and are therefore sometimes called "benzoxazine-based hardeners." Specific examples of benzoxazine resins include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation, "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0044] Thiol resins, when combined with epoxy resins, can react with the epoxy resin to harden the resin composition, and are therefore sometimes called "thiol-based hardeners." Examples of thiol resins include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0045] The active group equivalent of the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The active group equivalent is the mass of the curing agent per equivalent of the active group.
[0046] When the number of epoxy groups in the epoxy resin is 1, the number of active groups in the curing agent is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.5 or more, and preferably 5.0 or less, more preferably 4.0 or less, and particularly preferably 3.0 or less. The "number of epoxy groups in the epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. The "number of active groups in the curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the curing agent present in the resin composition by the active group equivalent.
[0047] The amount of the curing agent in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 5% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the amount of the curing agent is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0048] The amount of the curing agent in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, particularly preferably 60% by mass or less, when the resin component in the resin composition is taken as 100% by mass. When the amount of the curing agent is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0049] A compound having an ethylenically unsaturated bond can be used as the radical polymerizable resin. Thus, the radical polymerizable resin can have a radical polymerizable group containing an ethylenically unsaturated bond. Examples of the radical polymerizable group include unsaturated hydrocarbon groups such as vinyl group, allyl group, 3-cyclohexenyl group, 3-cyclopentenyl group, 2-vinylphenyl group, 3-vinylphenyl group, and 4-vinylphenyl group; and α,β-unsaturated carbonyl groups such as acryloyl group, methacryloyl group, and maleimide group (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group). The number of radical polymerizable groups contained in one molecule of the radical polymerizable resin may be one, but is preferably two or more. The radical polymerizable resin may be used alone or in combination of two or more types.
[0050] A preferred example of the radical polymerizable resin is a styrene-based radical polymerizable resin. The styrene-based radical polymerizable resin can be a compound having one or more, preferably two or more, vinyl groups directly bonded to an aromatic carbon atom. Examples of the styrene-based radical polymerizable resin include low molecular weight (molecular weight less than 1000) styrene-based compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; high molecular weight (molecular weight 1000 or more) styrene-based compounds such as vinylbenzyl-modified polyphenylene ether resin and styrene-divinylbenzene copolymer; and the like.
[0051] The styrene radical polymerizable resin is preferably a modified polyphenylene ether resin having a vinylphenyl group. The vinylphenyl group may include a 2-vinylphenyl group, a 3-vinylphenyl group, a 4-vinylphenyl group, or a group in which the aromatic carbon atom is further substituted with one or more alkyl groups. Among them, the styrene radical polymerizable resin is particularly preferably a resin represented by the following formula (A-1).
[0052] [ka]
[0053] (In formula (A-1), R 11 and R 12 each independently represents an alkyl group; R 13 , R 14 , R 21 , R 22 , R 23 and R 24 each independently represents a hydrogen atom or an alkyl group; R 31 and R 32 each independently represents a vinylphenyl group; Y1 is a single bond, -C(R y )2-, -O-, -CO-, -S-, -SO-, or -SO2-; R y each independently represents a hydrogen atom or an alkyl group; Y 2 represents a single bond or an alkylene group; p represents 0 or 1; q and r each independently represent an integer of 1 or more. The q units and r units may be the same or different for each unit.
[0054] In formula (A-1), R 11 and R 12 each independently represents an alkyl group, and is preferably a methyl group.
[0055] In formula (A-1), R 13 and R 14 each independently represents a hydrogen atom or an alkyl group, and is preferably a hydrogen atom.
[0056] In formula (A-1), R 21 and R 22 each independently represents a hydrogen atom or an alkyl group, preferably a hydrogen atom or a methyl group, and more preferably a methyl group.
[0057] In formula (A-1), R 23 and R 24 each independently represents a hydrogen atom or an alkyl group, and is preferably a hydrogen atom or a methyl group.
[0058] In formula (A-1), R 31 and R 32 each independently represents a vinylphenyl group.
[0059] In formula (A-1), Y 2represents a single bond or an alkylene group. The alkylene group refers to a linear, branched, and / or cyclic divalent aliphatic saturated hydrocarbon group. The alkylene group is preferably an alkylene group having 1 to 14 carbon atoms, more preferably an alkylene group having 1 to 10 carbon atoms, and particularly preferably an alkylene group having 1 to 6 carbon atoms. Examples of the alkylene group include -CH2-, -CH2-CH2-, -CH(CH3)-, -CH2-CH2-CH2-, -CH2-CH(CH3)-, -CH(CH3)-CH2-, -C(CH3)2-, and the like. Preferably, Y 2 is an alkylene group (particularly preferably -CH2-).
[0060] In formula (A-1), Y 1 is a single bond, -C(R y )2-, -O-, -CO-, -S-, -SO-, or -SO2-, and preferably a single bond, -C(R y ) 2- or -O-, and particularly preferably a single bond. y each independently represents a hydrogen atom or an alkyl group, and is preferably a hydrogen atom or a methyl group.
[0061] In formula (A-1), p represents 0 or 1, and is preferably 1.
[0062] In formula (A-1), q and r each independently represent an integer of 1 or more, preferably an integer of 1-200, and more preferably an integer of 1-100.
[0063] Specific examples of the resin represented by formula (A-1) include the resin represented by the following formula (A-1-1): Examples of the resin represented by formula (A-1-1) include "OPE-2St 1200" and "OPE-2St 2200" (vinylbenzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Company, Inc.
[0064] [ka]
[0065] Another preferred radical polymerizable resin is, for example, a maleimide radical polymerizable resin. The maleimide radical polymerizable resin may be a compound having one or more, preferably two or more, maleimide groups. The maleimide radical polymerizable resin may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or an aromatic maleimide compound containing an aromatic amine skeleton. Among them, the maleimide radical polymerizable resin is particularly preferably a resin represented by the following formula (A-2).
[0066] [ka]
[0067] (In formula (A-2), R a each independently represents a hydrogen atom or an alkyl group; ring E, ring F and ring G each independently represent an aromatic ring which may have a substituent; Z is independently a single bond, -C(R z )2-, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, or -NHCO-; R z each independently represents a hydrogen atom or an alkyl group; s represents an integer equal to or greater than 1; Each t is independently 0 or 1; Each u independently represents 0, 1, 2 or 3. The s units, t units and u units may be the same or different for each unit.
[0068] In formula (A-2), R a each independently represents a hydrogen atom or an alkyl group, preferably a hydrogen atom or a methyl group, and more preferably a hydrogen atom.
[0069] In formula (A-2), ring E, ring F and ring G each independently represent an aromatic ring which may have a substituent, preferably a benzene ring which may have a substituent, more preferably a benzene ring which may be substituted with a group selected from an alkyl group and an aryl group, and particularly preferably an unsubstituted benzene ring.
[0070] In formula (A-2), each Z is independently a single bond, -C(R z )2-, -O-, -CO-, -S-, -SO-, -SO2-, -CONH-, or -NHCO-, and preferably a single bond, -C(R z )2- or -O-, more preferably a single bond or -C(R z )2-, and particularly preferably a single bond. z each independently represents a hydrogen atom or an alkyl group, and is preferably a hydrogen atom or a methyl group.
[0071] In formula (A-2), s represents an integer of 1 or more, and is preferably an integer of 1-10.
[0072] In formula (A-2), each t is independently 0 or 1, and is preferably 1.
[0073] In formula (A-2), each u is independently 0, 1, 2 or 3, preferably 0, 1 or 2, more preferably 0 or 1, and particularly preferably 1.
[0074] Specific examples of the resin represented by formula (A-2) include the resin represented by the following formula (A-2-1): The resin represented by formula (A-2-1) is, for example, "MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd.
[0075] [ka]
[0076] Further preferred radical polymerizable resins include, for example, (meth)acrylic radical polymerizable resins. The (meth)acrylic radical polymerizable resins can be compounds having one or more, preferably two or more, acryloyl groups and / or methacryloyl groups. Examples of the (meth)acrylic radical polymerizable resins include cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonaphthalene di(meth)acrylate, 1,2-diphenylmethane di(meth)acrylate, 1,3-diphenylmethane di(meth)acrylate, 1,4-diphenylmethane di(meth)acrylate, 1,5-diphenylmethane di(meth)acrylate, 1,6-diphenylmethane di(meth)acrylate, 1,8-diphenylmethane di(meth)acrylate, 1,9-diphenylmethane ...5-diphenylmethane di(meth)acrylate, 1,6-diphenylmethane di(meth)acrylate, 1,7-diphenylmethane di(meth)acrylate, 1,8 Aliphatic (meth)acrylic acid ester compounds having a low molecular weight (molecular weight less than 1000), such as nandiol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerin tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; dioxane glycol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, Examples of the ether-containing (meth)acrylic acid ester compound include low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylic acid ester compounds such as 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, and propoxylated bisphenol A di(meth)acrylate; low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylic acid ester compounds such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; and high molecular weight (molecular weight 1000 or more) acrylic acid ester compounds such as (meth)acrylic-modified polyphenylene ether resin.Commercially available (meth)acrylic radical polymerizable resins include, for example, "A-DOG" (dioxane glycol diacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd., "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dioxane glycol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic-modified polyphenylene ether) manufactured by SABIC Innovative Plastics.
[0077] Yet another preferred radical polymerizable resin is, for example, an allyl radical polymerizable resin. The allyl radical polymerizable resin can be a compound having one or more, preferably two or more, allyl groups. Examples of allyl radical polymerizable resins include aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, and diallyl 2,3-naphthalenecarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; epoxy-containing aromatic allyl compounds such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; benzoxazine-containing aromatic allyl compounds such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; and allyl silane compounds such as diallyl diphenyl silane. Commercially available allyl radical polymerizable resins include, for example, "TAIC" (1,3,5-triallyl isocyanurate) manufactured by Nippon Kasei Chemical Industry Co., Ltd., "DAD" (diallyl diphenate) manufactured by Nisshoku Techno Fine Chemical Co., Ltd., "TRIAM-705" (triallyl trimellitate) manufactured by Wako Pure Chemical Industries, Ltd., trade name "DAND" (2,3-naphthalene carboxylate diallyl) manufactured by Nippon Distillation Industry Co., Ltd., "ALP-d" (bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane) manufactured by Shikoku Kasei Corporation, "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd., and "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Kasei Corporation.
[0078] Moreover, as the radical polymerizable resin, those described in the section on photocurable resins may be used.
[0079] The ethylenically unsaturated bond equivalent of the radical polymerizable resin is preferably 20 g / eq. to 3000 g / eq., more preferably 50 g / eq. to 2500 g / eq., further preferably 70 g / eq. to 2000 g / eq., and particularly preferably 90 g / eq. to 1500 g / eq. The ethylenically unsaturated bond equivalent represents the mass of the radical polymerizable resin per equivalent of the ethylenically unsaturated bond.
[0080] The weight average molecular weight (Mw) of the radical polymerizable resin is preferably 40000 or less, more preferably 10000 or less, further preferably 5000 or less, and particularly preferably 3000 or less. The lower limit is not particularly limited, but may be, for example, 150 or more.
[0081] The amount of the radical polymerizable resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1.0% by mass or more, and is preferably 10% by mass or less, more preferably 5.0% by mass or less, particularly preferably 3.0% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the amount of the radical polymerizable resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0082] The amount of the radical polymerizable resin in the resin composition is preferably 0.1% by mass or more, more preferably 1.0% by mass or more, particularly preferably 2.0% by mass or more, and is preferably 15% by mass or less, more preferably 10% by mass or less, particularly preferably 8.0% by mass or less, when the resin component in the resin composition is taken as 100% by mass. When the amount of the radical polymerizable resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0083] The photocurable resin may be a resin that can be cured when exposed to light. An example of the photocurable resin is a radical polymerizable resin. The photocurable resin may be used alone or in combination of two or more kinds.
[0084] The radical polymerizable resin as the photocurable resin may be any of those described in the section on thermosetting resins. From the viewpoint of enabling development with an alkaline developer, the radical polymerizable resin as the photocurable resin is preferably a resin having an ethylenically unsaturated bond and a carboxyl group.
[0085] The resin having an ethylenically unsaturated bond and a carboxyl group may have a combination of a radical polymerizable group containing an ethylenically unsaturated bond and a carboxyl group. Examples of the radical polymerizable group include those mentioned above. Among them, a (meth)acryloyl group is preferable. The number of radical polymerizable groups per resin molecule may be one or two or more. When the resin contains two or more radical polymerizable groups per molecule, the radical polymerizable groups may be the same or different. In addition, the number of carboxyls per resin molecule may be one or two or more.
[0086] The resin having an ethylenically unsaturated bond and a carboxyl group preferably contains a naphthalene skeleton. The resin having an ethylenically unsaturated bond and a carboxyl group may contain one naphthalene skeleton or may contain two or more naphthalene skeletons in one molecule. In addition, the resin having an ethylenically unsaturated bond and a carboxyl group preferably has two or less radical polymerizable groups per naphthalene skeleton. Furthermore, the radical polymerizable group is preferably contained in a substituent of the naphthalene skeleton. In addition, the resin having an ethylenically unsaturated bond and a carboxyl group preferably has two or less carboxyl groups per naphthalene skeleton. Furthermore, the carboxyl group is preferably contained in a substituent of the naphthalene skeleton.
[0087] A preferred resin having an ethylenically unsaturated bond and a carboxyl group is a resin containing a structure represented by the following formula (A-3). The resin having an ethylenically unsaturated bond and a carboxyl group may have only one structure represented by the following formula (A-3), or may have a plurality of structures. The number of structures represented by formula (A-3) per molecule of the resin having an ethylenically unsaturated bond and a carboxyl group is preferably 1 to 10, more preferably 1 to 6. In formula (A-3), R 1 may be bonded to any available carbon atom among the carbon atoms contained in the naphthalene skeleton. 1 may be bonded to a carbon atom of the same benzene ring or to a carbon atom of a different benzene ring with respect to the terminal bond. The terminal bond is a bond bonded to the naphthalene ring that is selected from the group consisting of R 1 Bonds and ORs attached to 0 Specifically, it represents the bond drawn on the left end of formula (A-3). For example, the terminal bond in the naphthalene skeleton and R 1 The combination of positions of the bond bonded to may be 1,2-positions, 1,3-positions, 1,4-positions, 1,5-positions, 1,6-positions, 1,7-positions, 1,8-positions, 2,3-positions, 2,6-positions, and 2,7-positions.
[0088] [ka]
[0089] In formula (A-3), R 1 and R 2 R each independently represents an alkylene group which may have a substituent. 1 and R 2 The number of carbon atoms in R is usually 1 to 20, preferably 1 to 10, and more preferably 1 to 6. The alkylene group may be linear or branched. Examples of the alkylene group include a methylene group, an ethylene group, a propylene group, and a butylene group, and the methylene group is preferred. 1 and R 2Examples of the substituent that may be possessed by the group include a halogen atom, an alkyl group, an alkoxy group, an aryl group, an arylalkyl group, a silyl group, an acyl group, an acyloxy group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, and an oxo group.
[0090] In formula (A-3), X represents an arylene group which may have a substituent. The number of carbon atoms of X is usually 6 to 30, preferably 6 to 20, and more preferably 6 to 10. Examples of the arylene group include a phenylene group, an anthracenylene group, a phenanthrenylene group, and a biphenylene group, and a phenylene group is preferable. Examples of the substituent that X may have include R 1 and R 2 The same examples of the substituents that may be possessed by the group may be mentioned.
[0091] In formula (A-3), a represents 0 or 1, and is preferably 1. Here, a is the number of groups X.
[0092] In formula (A-3), b represents 0 or 1. In addition, in formula (A-3), c represents 0 or 1. Here, b and c each represent a group R 1 and group R 2 However, b and c are such that b+c is not 0. It is preferable that both b and c are 1.
[0093] In formula (A-3), OR 0 R represents a substituent on the naphthalene skeleton. 0 Each of R independently represents an organic group containing a radical polymerizable group and a carboxyl group. 0 preferably represents a group represented by the following formula (A-4).
[0094] [ka]
[0095] In formula (A-4), R 3 R represents a trivalent group. 3Preferably, R represents a trivalent hydrocarbon group which may have a substituent (provided that a heteroatom may be present between the carbon-carbon bonds (CC bonds)). 3 R is preferably a trivalent aliphatic hydrocarbon group which may have a substituent. 3 The substituents which may be carried by R 1 and R 2 The same examples of the substituents that may be possessed by the group may be mentioned.
[0096] In formula (A-4), R 4 represents an organic group containing a radical polymerizable group. A preferred example of the organic group containing a radical polymerizable group is a (meth)acryloyloxy group. The term "(meth)acryloyloxy group" includes an acryloyloxy group, a methacryloyloxy group, and a combination thereof.
[0097] In formula (A-4), R 5 represents an organic group containing a carboxyl group. An example of an organic group containing a carboxyl group is -OCO-R 6 -COOH, where R 6 R represents a divalent group. 6 R is preferably a divalent hydrocarbon group which may have a substituent. 6 The number of carbon atoms in R is usually 1 to 30, preferably 1 to 20, and more preferably 1 to 6. Examples of the divalent hydrocarbon group include linear or branched acyclic alkylene groups such as methylene, ethylene, propylene, and butylene groups; saturated or unsaturated divalent alicyclic hydrocarbon groups; and arylene groups such as phenylene and naphthylene groups. Among these, divalent alicyclic hydrocarbon groups and arylene groups are preferred, with 4-cyclohexenylene and phenylene groups being particularly preferred. In addition, R 6 The substituents which may be carried by R 1 and R 2 Examples of the substituents that may be included in -OCO-R are the same as those in 6 -CO-R in -COOH 6-COOH may be a residue of a carboxylic acid anhydride, such as maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, or benzophenonetetracarboxylic dianhydride.
[0098] In formula (A-3), d is usually an integer of 1 to 6, preferably 1 to 3, and more preferably 1 to 2. Here, d is a group OR 0 Represents the number of.
[0099] The weight average molecular weight of the resin having an ethylenically unsaturated bond and a carboxyl group is preferably 500 or more, more preferably 1000 or more, even more preferably 1500 or more, and even more preferably 2000 or more, from the viewpoint of film-forming properties. The upper limit is preferably 10000 or less, more preferably 8000 or less, and even more preferably 7500 or less, from the viewpoint of developability.
[0100] From the viewpoint of keeping the solubility in an alkaline developer within an appropriate range, the acid value of the resin having an ethylenically unsaturated bond and a carboxyl group is preferably 0.1 mgKOH / g or more, more preferably 0.5 mgKOH / g or more, particularly preferably 1 mgKOH / g or more, and is preferably 150 mgKOH / g or less, more preferably 120 mgKOH / g or less, particularly preferably 100 mgKOH / g or less.
[0101] The acid value can be measured by the following method. First, after weighing out about 1 g of the resin solution to be measured, 30 g of acetone is added to the resin solution to dissolve the resin solution uniformly. Next, an appropriate amount of phenolphthalein as an indicator is added to the solution, and titration is performed using a 0.1 N ethanolic KOH solution. Then, the acid value is calculated by the following formula (X1). A=Vf×5.611 / (Wp×I) (X1)
[0102] In the above formula (X1), A represents the acid value [mgKOH / g], Vf represents the titration amount [mL] of the KOH solution, Wp represents the mass [g] of the measured resin solution, and I represents the proportion [mass%] of the non-volatile components of the measured resin solution.
[0103] The amount of the radical polymerizable resin as the photocurable resin is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the amount of the radical polymerizable resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0104] The amount of the radically polymerizable resin as the photocurable resin is preferably 20% by mass or more, more preferably 30% by mass or more, particularly preferably 40% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, particularly preferably 65% by mass or less, when the resin component in the resin composition is taken as 100% by mass. When the amount of the radically polymerizable resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0105] The amount of the (A) curable resin in the resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, particularly preferably 30% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less, particularly preferably 50% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the amount of the (A) curable resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0106] The amount of the (A) curable resin in the resin composition is preferably 60% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, and is preferably 97% by mass or less, more preferably 95% by mass or less, particularly preferably 90% by mass or less, when the resin component in the resin composition is taken as 100% by mass. When the amount of the (A) curable resin is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0107] [3.(B) Inorganic filler] The resin composition according to the first embodiment of the present invention contains an inorganic filler (B) as component (B). The inorganic filler (B) is usually contained in the resin composition in the form of particles.
[0108] (B) Inorganic filler may be an inorganic compound, such as silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate.
[0109] In addition, inorganic complex oxides may be used as the material of the inorganic filler (B). The inorganic complex oxide refers to an oxide containing two or more kinds of atoms selected from the group consisting of metal atoms and metalloid atoms. As such an inorganic complex oxide, an oxide containing a combination of silicon and one or more kinds of atoms selected from the group consisting of metal atoms and metalloid atoms other than silicon is preferable. Examples of metal atoms to be combined with silicon include aluminum, lead, nickel, cobalt, copper, zinc, zirconium, iron, lithium, magnesium, barium, potassium, calcium, titanium, boron, sodium, etc., and among them, aluminum is particularly preferable. Therefore, as the inorganic complex oxide, an oxide containing silicon and aluminum is preferable, and an aluminosilicate is particularly preferable.
[0110] Among these materials for the (B) inorganic filler, silica, alumina and aluminosilicate are preferred, and silica is particularly preferred. The (B) inorganic filler may be used alone or in combination of two or more kinds.
[0111] (B) inorganic fillers can be classified into (B-1) hollow inorganic fillers having voids inside and (B-2) solid inorganic fillers having no voids inside. (B) inorganic fillers preferably contain (B-1) hollow inorganic fillers. (B-1) hollow inorganic fillers have voids inside the particles of the (B-1) hollow inorganic fillers, so that they generally have a smaller specific gravity than (B-2) solid inorganic fillers. Therefore, when (B) inorganic fillers contain (B-1) hollow inorganic fillers, the specific gravity of the cured product of the resin composition can be reduced. In addition, when (B-1) hollow inorganic fillers are used, the relative dielectric constant of the cured product of the resin composition can usually be reduced.
[0112] The (B-1) hollow inorganic filler may be a monohollow particle having only one hole inside the particle, a multihollow particle having two or more holes inside the particle, or a combination of a monohollow particle and a multihollow particle.
[0113] Since the hollow inorganic filler (B-1) has pores, it usually has a porosity of more than 0 volume%. From the viewpoint of effectively improving the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition, the porosity of the hollow inorganic filler (B-1) is preferably 10 volume% or more, more preferably 15 volume% or more, and particularly preferably 20 volume% or more. In addition, from the viewpoint of the mechanical strength of the cured product of the resin composition, the porosity of the hollow inorganic filler (B-1) is preferably 95 volume% or less, more preferably 90 volume% or less, and particularly preferably 85 volume% or less.
[0114] The porosity P (volume %) of a particle is defined as the volume ratio of the total volume of one or more pores present inside the particle to the total volume of the particle based on the outer surface of the particle (total volume of pores / volume of particle). This porosity P is calculated by multiplying the measured value of the actual density D of the particle by the volume ratio of the particle. M (g / cm 3 ), and the theoretical density of the material that forms the particle D T (g / cm 3 ) can be calculated using the following formula (X2).
[0115]
number
[0116] (B) Hollow inorganic particles generally have voids formed within the particles and an outer shell formed of an inorganic material surrounding the voids. Usually, the voids are separated from the outside of the particle by the outer shell. In this case, it is desirable that the voids do not communicate with the outside of the particle. Therefore, it is desirable that the outer shell is a non-porous shell that does not have holes that communicate the voids with the outside of the particle. The fact that the outer shell is non-porous can be confirmed by observation with a transmission electron microscope (TEM).
[0117] The average particle size of the hollow inorganic filler (B-1) is preferably 0.01 μm or more, more preferably 0.1 μm or more, particularly preferably 0.3 μm or more, and is preferably 5 μm or less, more preferably 4 μm or less, particularly preferably 3 μm or less. When the average particle size of the hollow inorganic filler (B-1) is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0118] The average particle size of particles can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of particles is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample of the inorganic filler can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the inorganic filler by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the volume-based particle size distribution of the inorganic filler is measured using a flow cell method, and the average particle size can be calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0119] The BET specific surface area of the hollow inorganic filler (B-1) is preferably 1 m 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 5m 2 / g or more, preferably 100m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 30m 2 / g or less. (B-1) When the BET specific surface area of the hollow inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved. The BET specific surface area of the particles can be measured according to the BET method by adsorbing nitrogen gas onto the sample surface using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) and calculating the specific surface area using the BET multipoint method.
[0120] The (B-1) hollow inorganic filler may be a commercially available product. Examples of commercially available (B-1) hollow inorganic fillers include "Cellphears" and "MGH-005" manufactured by Pacific Cement Corporation; and "Esferique" and "BA-1" manufactured by JGC Catalysts and Chemicals. The (B-1) hollow inorganic filler may be one manufactured by a conventional method. To give a specific example, hollow silica particles, which are an example of the (B-1) hollow inorganic filler, may be manufactured by a method including the steps of: preparing an aqueous solution containing a substance capable of forming pores and a basic compound; mixing the aqueous solution with an alkoxysilane, stirring, and precipitating silica particles; removing the substance capable of forming pores from the silica particles to obtain a hollow silica precursor; and calcining the hollow silica precursor.
[0121] (B-1) The hollow inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. One type of surface treatment agent may be used alone, or two or more types may be used in any combination.
[0122] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0123] From the viewpoint of improving dispersibility, the degree of surface treatment with the surface treatment agent is preferably within a specific range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 8% by mass of the surface treatment agent, more preferably with 0.2% to 5% by mass of the surface treatment agent, and even more preferably with 0.3% to 3% by mass of the surface treatment agent.
[0124] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition, it is more preferable that the content is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0125] The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.
[0126] The amount (mass%) of the hollow inorganic filler (B-1) in the resin composition is preferably 5 mass% or more, more preferably 10 mass% or more, particularly preferably 15 mass% or more, and is preferably 80 mass% or less, more preferably 70 mass% or less, particularly preferably 60 mass% or less, when the non-volatile components in the resin composition are taken as 100 mass%. When the amount of the hollow inorganic filler (B-1) is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0127] The amount (volume %) of the hollow inorganic filler (B-1) in the resin composition is preferably 5 volume % or more, more preferably 10 volume % or more, particularly preferably 15 volume % or more, and is preferably 80 volume % or less, more preferably 70 volume % or less, particularly preferably 60 volume % or less, when the non-volatile components in the resin composition are taken as 100 volume %. When the amount of the hollow inorganic filler (B-1) is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0128] The inorganic filler (B) may contain a solid inorganic filler (B-2). Commercially available solid inorganic fillers (B-2) include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; and "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation.
[0129] The average particle size of the (B-2) solid inorganic filler is preferably 0.01 μm or more, more preferably 0.1 μm or more, particularly preferably 0.3 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less, particularly preferably 3 μm or less.
[0130] The BET specific surface area of the (B-2) solid inorganic filler is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, particularly preferably 1m 2 / g or more, preferably 100m 2 / g or less, more preferably 70m 2 / g or less, particularly preferably 40m 2 / g or less.
[0131] The (B-2) solid inorganic filler, like the (B-1) hollow inorganic filler, is preferably treated with a surface treatment agent.
[0132] The amount (mass %) of the (B-2) solid inorganic filler in the resin composition may be 0 mass % or more than 0 mass %, and is preferably 10 mass % or more, more preferably 20 mass % or more, particularly preferably 30 mass % or more, and is preferably 50 mass % or less, more preferably 45 mass % or less, and particularly preferably 40 mass % or less, assuming that the non-volatile components in the resin composition are 100 mass %.
[0133] The amount (volume %) of the (B-2) solid inorganic filler in the resin composition may be 0 volume % or more, and is preferably 5 volume % or more, more preferably 10 volume % or more, and particularly preferably 20 volume % or more, and is preferably 50 volume % or less, more preferably 40 volume % or less, and particularly preferably 30 volume % or less, assuming that the non-volatile components in the resin composition are 100 volume %.
[0134] The ratio of pores contained in the entire (B) inorganic filler, including both the (B-1) hollow inorganic filler and the (B-2) solid inorganic filler, is determined as the porosity (volume %) of the (B) inorganic filler. The porosity (volume %) of the (B) inorganic filler is a representative value that represents the ratio of pores to the volume of the (B) inorganic filler on a volume basis, and is expressed as "total volume of pores / total volume of the (B) inorganic filler". The specific range of the porosity of the (B) inorganic filler is preferably 10 volume % or more, more preferably 15 volume % or more, particularly preferably 20 volume % or more, and is preferably 80 volume % or less, more preferably 70 volume % or less, particularly preferably 60 volume % or less.
[0135] The average particle size of the entire (B) inorganic filler including both the (B-1) hollow inorganic filler and the (B-2) solid inorganic filler is preferably 0.01 μm or more, more preferably 0.1 μm or more, particularly preferably 0.3 μm or more, and is preferably 5 μm or less, more preferably 4 μm or less, particularly preferably 3 μm or less. When the average particle size of the (B) inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer including the cured product of the resin composition can be effectively improved.
[0136] The BET specific surface area of the entire inorganic filler (B) including both the hollow inorganic filler (B-1) and the solid inorganic filler (B-2) is preferably 1 m 2 / g or more, more preferably 2m 2 / g or more, particularly preferably 5m 2 / g or more, preferably 100m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 30m 2 When the BET specific surface area of the (B) inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0137] The amount (mass%) of the (B) inorganic filler in the resin composition is preferably 20 mass% or more, more preferably 30 mass% or more, particularly preferably 40 mass% or more, and is preferably 80 mass% or less, more preferably 70 mass% or less, particularly preferably 60 mass% or less, when the non-volatile components in the resin composition are taken as 100 mass%. When the amount of the (B) inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0138] The amount (volume %) of the (B) inorganic filler in the resin composition is preferably 20 volume % or more, more preferably 30 volume % or more, particularly preferably 40 volume % or more, and is preferably 80 volume % or less, more preferably 75 volume % or less, particularly preferably 70 volume % or less, when the non-volatile components in the resin composition are taken as 100 volume %. When the amount of the (B) inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0139] [4.(C)Organic particles] The resin composition according to the first embodiment of the present invention preferably contains (C) organic particles as component (C) in combination with (A) the curable resin and (B) the inorganic filler. The (C) organic particles are present in particulate form in the resin composition and are usually included in the cured product while maintaining the particulate form.
[0140] Since the (C) organic particles contain an organic material, they usually have a larger thermal expansion coefficient than the (B) inorganic filler and a smaller specific gravity than the (B) inorganic filler. Therefore, by using the (C) organic particles, it is possible to adjust the thermal expansion coefficient and specific gravity of the cured product of the resin composition. In addition, since the (C) organic particles generally tend to have higher flexibility than the (B) inorganic filler, the (C) organic particles can increase the stress resistance of the cured product of the resin composition.
[0141] As the (C) organic particles, particles having a uniform composition throughout the particle may be used, but particles having a non-uniform composition may also be used. For example, a multilayer particle having a shell portion and an internal portion formed in the shell portion is preferred. The multilayer particle may also include a portion other than the shell portion and the internal portion. For example, the multilayer particle may further include an arbitrary portion in the internal portion. For example, the multilayer particle may also include an arbitrary layer between the shell portion and the internal portion. Since the internal portion is usually covered by the shell portion, the multilayer particle can be highly dispersed in the resin composition regardless of the composition of the internal portion, and therefore, the degree of freedom of the composition of the internal portion can be increased. Therefore, the internal portion having a composition suitable for the insulating layer can be adopted, so that the characteristics of the insulating layer can be improved. The multilayer particle referred to here does not necessarily refer only to those in which the shell portion and the internal portion can be clearly distinguished, but also includes those in which the boundary between the shell portion and the internal portion is unclear, and the internal portion does not have to be completely covered by the shell portion.
[0142] The shell part of the multi-layer particle is usually formed by a polymer. The polymer forming the shell part may be a homopolymer as a polymer of one type of monomer, or a copolymer as a copolymer of two or more types of monomers. It is preferable to select the type of polymer and its monomer forming the shell part that can suppress the aggregation of the (C) organic particles and disperse well in the resin composition. The specific type may depend on the composition of the (A) curable resin, but preferred examples of the monomer include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, and glycidyl (meth)acrylate; (meth)acrylic acid; N-substituted maleimides such as N-methylmaleimide and N-phenylmaleimide; maleimide; α,β-unsaturated carboxylic acids such as maleic acid and itaconic acid; aromatic vinyl compounds such as styrene, 4-vinyltoluene, and α-methylstyrene; and (meth)acrylonitrile. These monomers may be used alone or in combination of two or more.
[0143] The built-in part of the multilayer particle preferably contains an organic material different from that contained in the shell part. The multilayer particle having a built-in part containing an organic material may have a core part corresponding to the built-in part and a shell part covering the core part, and may be called a "core-shell particle". Among them, the built-in part preferably contains a rubber component. When the organic particle (C) contains a multilayer particle containing a rubber component in the built-in part, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved. For example, a resin showing an elastic modulus of 1 GPa or less when a tensile test is performed at a temperature of 25°C and a humidity of 40% RH in accordance with the Japanese Industrial Standards (JIS K7161) can be used as the rubber component. In addition, for example, a resin having a glass transition temperature of preferably 0°C or less, more preferably -10°C or less, even more preferably -20°C or less, and particularly preferably -30°C or less can be used as the rubber component. The glass transition temperature can be measured by DSC (differential scanning calorimetry) at a heating rate of 10°C / min. These rubber components can be prepared, for example, as resins having one or more structures selected from a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure in the molecule.
[0144] Specific examples of the rubber component include silicone-based elastomers such as polydimethylsiloxane; olefin-based thermoplastic elastomers such as polybutadiene, polyisoprene, polychlorobutadiene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-diene terpolymer, and ethylene-propylene-butene terpolymer; and thermoplastic elastomers such as acrylic thermoplastic elastomers such as polypropyl(meth)acrylate, polybutyl(meth)acrylate, polycyclohexyl(meth)acrylate, and polyoctyl(meth)acrylate. Furthermore, silicone-based rubbers such as polyorganosiloxane rubber may be mixed into the rubber component.
[0145] In the multi-layered particles containing a rubber component, the amount of the rubber component is preferably 40% by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more. There is no particular upper limit, but from the viewpoint of sufficiently covering the built-in part with the shell part, it can be, for example, 95% by mass or less, 90% by mass, etc.
[0146] The multilayer particle having a built-in portion containing a rubber component can be produced, for example, by a production method including a step of preparing a core particle containing a rubber component, and a step of forming a shell portion by graft copolymerizing a monomer component copolymerizable with the rubber component contained in the core particle. In addition, the multilayer particle having a built-in portion containing a rubber component may be a commercially available product. Examples of commercially available products include "CHT" manufactured by Cheil Industries, Inc.; "B602" manufactured by UMGABS, Inc.; and "Paraloid EXL-2602", "Paraloid EXL-2603", "Paraloid EXL-2655", "Paraloid EXL-2311", "Paraloid-EXL2313", "Paraloid EXL-2315", "Paraloid KM-330", "Paraloid KM-336P", and "Paraloid KCZ- 201"; Mitsubishi Rayon's "Metabrene C-223A", "Metabrene E-901", "Metabrene S-2001", "Metabrene W-450A", and "Metabrene SRK-200"; Kaneka's "Kane Ace M-511", "Kane Ace M-600", "Kane Ace M-400", "Kane Ace M-580", and "Kane Ace MR-01"; Aica Kogyo's Staphyloids "AC3832" and "AC3816N", etc.
[0147] The built-in part of the multilayer particle may be a hollow part. That is, the multilayer particle may have a hollow part as a void surrounded by a shell part. Such a multilayer particle having a hollow part as a built-in part may be called a "hollow organic particle". When the (C) organic particle contains a multilayer particle including a hollow part as a built-in part, the impact peel resistance and impact crack resistance of the insulating layer including the cured product of the resin composition can be effectively improved.
[0148] The multilayer particles containing hollow portions usually have a porosity of more than 0% by volume. From the viewpoint of effectively improving the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition, the porosity of the multilayer particles is preferably 10% by volume or more, more preferably 15% by volume or more, and particularly preferably 20% by volume or more. In addition, from the viewpoint of the mechanical strength of the cured product of the resin composition, the porosity of the multilayer particles is preferably 90% by volume or less, more preferably 90% by volume or less, and particularly preferably 80% by volume or less.
[0149] The multilayer particles containing hollow portions can be manufactured by the methods described in, for example, JP 2006-265394 A, JP 2007-238792 A, WO 2011 / 040376 A, JP 2016-190980 A, WO 2018 / 051794 A, and JP 2020-189978 A. The multilayer particles containing hollow portions may be commercially available products. Examples of commercially available products include "XX-5598Z" manufactured by Sekisui Chemical Co., Ltd.
[0150] The (C) organic particles may be used alone or in combination of two or more kinds.
[0151] The (C) organic particles may be treated with a surface treatment agent. Examples of the surface treatment agent for the (C) organic particles include inorganic acids such as hydrochloric acid, nitric acid, and sulfuric acid; carboxylic acids such as acetic acid, propionic acid, butyric acid, and acrylic acid; sulfonic acids such as p-toluenesulfonic acid, ethylsulfonic acid, and dodecylbenzenesulfonic acid; phosphoric acids such as polyoxyethylene alkyl ether phosphoric acid; organic acids such as phosphonic acid and phosphinic acid; silane coupling agents such as tetraethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, and 8-(meth)acryloxyoctyltrimethoxysilane; and isocyanate compounds such as ethyl isocyanate.
[0152] The average particle size of the (C) organic particles is preferably smaller than that of the (B-1) hollow inorganic filler. The specific average particle size of the (C) organic particles is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.10 μm or more, and is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably 1 μm or less. The average particle size of the (C) organic particles can be measured using a zeta potential particle size distribution measuring device.
[0153] The amount (mass%) of the (C) organic particles in the resin composition is preferably 0.5 mass% or more, more preferably 1.5 mass% or more, particularly preferably 2 mass% or more, and is preferably 20 mass% or less, more preferably 15 mass% or less, particularly preferably 10 mass% or less, when the non-volatile components in the resin composition are taken as 100 mass%. When the amount of the (C) organic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0154] The amount (volume %) of the (C) organic particles in the resin composition is preferably 0.5 volume % or more, more preferably 1.5 volume % or more, particularly preferably 2.0 volume % or more, and is preferably 20 volume % or less, more preferably 15 volume % or less, particularly preferably 10 volume % or less, when the non-volatile components in the resin composition are taken as 100 volume %. When the amount of the (C) organic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0155] The amount (mass%) of the (C) organic particles in the resin composition is preferably 1.0 mass% or more, more preferably 1.5 mass% or more, particularly preferably 2.0 mass% or more, and is preferably 30 mass% or less, more preferably 20 mass% or less, particularly preferably 15 mass% or less, when the resin component in the resin composition is taken as 100 mass%. When the amount of the (C) organic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0156] The mass ratio of the (C) organic particles to the (B-1) hollow inorganic filler in the resin composition ((C) organic particles / (B-1) hollow inorganic filler) is preferably 0.01 or more, more preferably 0.02 or more, particularly preferably 0.03 or more, and is preferably 0.50 or less, more preferably 0.40 or less, particularly preferably 0.30 or less. When the mass ratio ((C) organic particles / (B-1) hollow inorganic filler) is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0157] The volume ratio of the (C) organic particles to the (B-1) hollow inorganic filler in the resin composition ((C) organic particles / (B-1) hollow inorganic filler) is preferably 0.01 or more, more preferably 0.03 or more, particularly preferably 0.05 or more, and is preferably 0.50 or less, more preferably 0.30 or less, particularly preferably 0.20 or less. When the volume ratio ((C) organic particles / (B-1) hollow inorganic filler) is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0158] The total mass of the (C) organic particles and (B-1) hollow inorganic filler in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 15% by mass or more, and is preferably 80% by mass or less, more preferably 75% by mass or less, particularly preferably 70% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass. When the total mass of the (C) organic particles and (B-1) hollow inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0159] The total volume of the (C) organic particles and (B-1) hollow inorganic filler in the resin composition is preferably 10% by volume or more, more preferably 15% by volume or more, particularly preferably 20% by volume or more, and is preferably 85% by volume or less, more preferably 80% by volume or less, particularly preferably 75% by volume or less, when the non-volatile components in the resin composition are taken as 100% by volume. When the total volume of the (C) organic particles and (B-1) hollow inorganic filler is within the above range, the impact peel resistance and impact crack resistance of the insulating layer containing the cured product of the resin composition can be effectively improved.
[0160] [5. (D) Curing accelerator] The resin composition according to the first embodiment of the present invention may further contain a curing accelerator (D) as an optional component in combination with the above-mentioned components (A) to (C). The curing accelerator (D) as the component (D) does not include those corresponding to the above-mentioned components (A) to (C). The curing accelerator (D) functions as a curing catalyst that accelerates the curing of the curable resin (A).
[0161] As the (D) curing accelerator, an appropriate one can be used depending on the type of the (A) curing resin. For example, when the (A) curing resin contains an epoxy resin, examples of the (D) curing accelerator that can accelerate the curing of the epoxy resin include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. The (D) curing accelerators may be used alone or in combination of two or more.
[0162] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.
[0163] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].
[0164] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.
[0165] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0166] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0167] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0168] The amount of the (D) curing accelerator in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and particularly preferably 0.05% by mass or more, and is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.2% by mass or less, assuming that the non-volatile components in the resin composition are 100% by mass.
[0169] The amount of the (D) curing accelerator in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and particularly preferably 0.10% by mass or more, and is preferably 2.0% by mass or less, more preferably 1.0% by mass or less, and particularly preferably 0.5% by mass or less, based on the resin component in the resin composition being 100% by mass.
[0170] [6. (E) Polymerization initiator] The resin composition according to the first embodiment of the present invention may further contain a polymerization initiator (E) as an optional component in combination with the above-mentioned components (A) to (D). The polymerization initiator (E) as the component (E) does not include those corresponding to the above-mentioned components (A) to (D). The polymerization initiator (E) may be used alone or in combination of two or more kinds.
[0171] The type of the polymerization initiator (E) can be selected depending on the type of the curable resin (A). For example, when the curable resin (A) contains a radical polymerizable resin as a photocurable resin, it is preferable to use a photopolymerization initiator as the polymerization initiator (E).
[0172] Examples of the polymerization initiator (E) include α-aminoalkylphenone-based polymerization initiators such as 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-[4-(4-morpholinyl)phenyl]-1-butanone, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one; oxime ester-based polymerization initiators such as ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, and 1-(O-acetyloxime); benzophenone, methylbenzophenone, o-benzoylbenzoic acid, benzoyl ethyl ether, and 2,2-diethoxyacetophenone; Examples of the photopolymerization initiator include 2,4-diethylthioxanthone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl-(2,4,6-trimethylbenzoyl)phenylphosphinate, 4,4'-bis(diethylamino)benzophenone, 1-hydroxy-cyclohexyl-phenyl ketone, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, a sulfonium salt-based photopolymerization initiator can also be used.
[0173] Commercially available examples of the (E) polymerization initiator include "Omnirad907", "Omnirad369", "Omnirad379", "Omnirad819", and "OmniradTPO" manufactured by IGM, "IrgacureTPO", "IrgacureOXE-01", and "IrgacureOXE-02" manufactured by BASF, and "N-1919" manufactured by ADEKA.
[0174] The amount of the (E) polymerization initiator in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 1% by mass or more, and is preferably 10% by mass or less, more preferably 7% by mass or less, and particularly preferably 5% by mass or less, assuming that the non-volatile components in the resin composition are 100% by mass.
[0175] The amount of the (E) polymerization initiator in the resin composition may be 0% by mass or may be more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less, assuming that the resin component in the resin composition is 100% by mass.
[0176] [7.(F) Thermoplastic resin] The resin composition according to the first embodiment of the present invention may further contain a thermoplastic resin (F) as an optional component in combination with the above-mentioned components (A) to (E). The thermoplastic resin (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E).
[0177] Examples of the (F) thermoplastic resin include phenoxy resin, polyimide resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. The (F) thermoplastic resin may be used alone or in combination of two or more kinds.
[0178] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.
[0179] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.
[0180] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0181] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.
[0182] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0183] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0184] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0185] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0186] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.
[0187] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.
[0188] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.
[0189] The weight average molecular weight (Mw) of the (F) thermoplastic resin is preferably greater than 5,000, more preferably 8,000 or more, even more preferably 10,000 or more, and particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, and particularly preferably 50,000 or less.
[0190] The amount of the (F) thermoplastic resin in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less, assuming that the non-volatile components in the resin composition are 100% by mass.
[0191] The amount of the (F) thermoplastic resin in the resin composition may be 0% by mass or may be greater than 0% by mass, and is preferably 0.1% by mass or more, more preferably 1% by mass or more, and particularly preferably 2% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, and particularly preferably 10% by mass or less, assuming that the resin component in the resin composition is 100% by mass.
[0192] 8.(G) Optional Additives The resin composition according to the first embodiment of the present invention may further contain an optional additive (G) as an optional non-volatile component in combination with the above-mentioned components (A) to (F). Examples of the optional additive (G) include organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, and triazine-based adhesion imparters; and hindered phenol-based antioxidants. Antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; photopolymerization initiators such as tertiary amines; photosensitizers such as pyrarizones, anthracenes, coumarins, xanthones, and thioxanthones. (G) Optional additives may be used alone or in combination of two or more.
[0193] 9. (I) Solvents The resin composition according to the first embodiment of the present invention may further contain (I) a solvent as an optional volatile component in combination with the non-volatile components such as the above-mentioned components (A) to (G). As the (I) solvent, an organic solvent is usually used. As the organic solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, anisole, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methyl methoxypropionate, etc. Examples of suitable solvents include ether ester solvents such as ethyl acetate, ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide solvents such as dimethyl sulfoxide, nitrile solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (I) The solvent may be used alone or in combination of two or more.
[0194] The amount of (I) solvent is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, etc., or it can be 0 mass%.
[0195] [10. Specific Gravity of Cured Resin Composition] The cured product obtained by curing the resin composition according to the first embodiment of the present invention has a specific gravity in a specific range. The specific range of the specific gravity of the cured product is usually 1.6 g / cm 3 Less than 1.58 g / cm 3 Less than or equal to 1.56 g / cm 3 The lower limit of the specific gravity of the cured product is preferably 1.0 g / cm 3 More preferably, 1.02 g / cm 3 More preferably, 1.05 g / cm 3 The resin composition which gives a cured product having a specific gravity in the above range can provide good impact peel resistance and impact crack resistance to an insulating layer which contains the cured product of the resin composition.
[0196] When the resin composition is a thermosetting resin composition that can be cured by heating, the cured product for which the specific gravity is evaluated is obtained by curing the resin composition at 180°C for 90 minutes. When the resin composition is a photocurable resin composition that can be cured by exposure to light, the cured product for which the specific gravity is evaluated is obtained by curing the resin composition at 1 J / cm 2 After irradiation with actinic rays, the composition is heated at 180° C. for 90 minutes. A specific method for obtaining the cured product may be the method described in the Examples below. The specific gravity of the cured product may be measured by the method described in the Examples below.
[0197] The specific gravity of the cured product of the resin composition can be adjusted by the composition of the resin composition. For example, the specific gravity can be increased by increasing the amount of (B) inorganic filler. In addition, the specific gravity of the cured product can be decreased by, for example, using a hollow inorganic filler (B-1) with a large porosity or increasing the amount of (B-1) hollow inorganic filler. Furthermore, the specific gravity of the cured product can be adjusted by adjusting the type and amount of (A) curable resin.
[0198] [11. Thermal expansion coefficient of cured resin composition] The cured product obtained by curing the resin composition according to the first embodiment of the present invention has a thermal expansion coefficient in a specific range. The specific range of the thermal expansion coefficient of the cured product is usually 40 ppm / °C or less, preferably 30 ppm / °C or less, and more preferably 25 ppm / °C or less. The lower limit of the thermal expansion coefficient of the cured product is preferably 5 ppm / °C or more, more preferably 10 ppm / °C or more, and particularly preferably 15 ppm / °C or more. The resin composition from which a cured product having a thermal expansion coefficient in the above range can provide good impact peel resistance and impact crack resistance of an insulating layer containing a cured product of the resin composition.
[0199] When the resin composition is a thermosetting resin composition that can be cured by heating, the cured product for which the thermal expansion coefficient is evaluated is obtained by curing the resin composition at 180°C for 90 minutes. When the resin composition is a photocurable resin composition that can be cured by exposure to light, the cured product for which the thermal expansion coefficient is evaluated is obtained by curing the resin composition at 180°C for 90 minutes. 2 After irradiation with actinic rays, the composition is heated at 180°C for 90 minutes. A specific method for obtaining a cured product may be the method described in the Examples below. The thermal expansion coefficient of the cured product is the average linear thermal expansion coefficient in the temperature range from 25°C to 150°C, and can be measured by thermomechanical analysis using a tensile load method under measurement conditions of a load of 1 g and a heating rate of 5°C / min. A specific method for measuring the thermal expansion coefficient of the cured product may be the method described in the Examples below.
[0200] The thermal expansion coefficient of the cured resin composition can be adjusted by the composition of the resin composition. For example, by increasing the amount of (B) inorganic filler, the thermal expansion coefficient can be reduced. Also, by increasing the amount of resin component, the thermal expansion coefficient can be increased. Furthermore, the thermal expansion coefficient can be changed by adjusting the type of inorganic filler and resin component.
[0201] [12. Resin composition according to the second embodiment] The resin composition according to the second embodiment of the present invention is the same as the resin composition according to the first embodiment of the present invention, except that: (i) the resin composition contains (C) organic particles; (ii) the (B) inorganic filler contains (B-1) hollow inorganic filler; (iii) the (B-1) hollow inorganic filler has a porosity within a specific range; (iv) the amount of the (B) inorganic filler relative to 100% by volume of the non-volatile components of the resin composition is within a specific range; (v) the amount of the (B-1) hollow inorganic filler relative to 100% by volume of the non-volatile components of the resin composition is within a specific range; and (vi) the specific gravity and thermal expansion coefficient of the cured product obtained by curing the resin composition do not have to be within a specific range.
[0202] The porosity range of the hollow inorganic filler (B-1) in the resin composition according to the second embodiment of the present invention is usually 10 volume % or more, and is preferably in the same range as the porosity of the hollow inorganic filler (B-1) in the resin composition according to the first embodiment. The amount of the inorganic filler (B) in the resin composition according to the second embodiment of the present invention is usually 40% by volume or more relative to 100% by volume of the non-volatile components of the resin composition, and is preferably in the same range as the amount of the inorganic filler (B) in the resin composition according to the first embodiment. Furthermore, the amount of the hollow inorganic filler (B-1) in the resin composition according to the second embodiment of the present invention is usually 10% by volume or more relative to 100% by volume of the non-volatile components of the resin composition, and is preferably in the same range as the amount of the hollow inorganic filler (B-1) in the resin composition according to the first embodiment. The specific gravity and thermal expansion coefficient of the cured product obtained by curing the resin composition according to the second embodiment of the present invention may be in a range different from the specific gravity and thermal expansion coefficient of the cured product of the resin composition according to the first embodiment, but are preferably in the same range. The specific gravity and thermal expansion coefficient of the cured product of the resin composition according to the second embodiment can be measured and adjusted by the same method as the specific gravity and thermal expansion coefficient of the cured product of the resin composition according to the first embodiment.
[0203] According to the resin composition according to the second embodiment of the present invention, it is possible to obtain the same advantages as those of the resin composition according to the first embodiment.
[0204] [13. Method for producing resin composition] In the following description, unless otherwise specified, the term "resin composition" refers to both the resin composition according to the first embodiment and the resin composition according to the second embodiment. The resin composition can be produced, for example, by mixing components that can be contained in the resin composition. The above-mentioned components may be mixed in part or in whole at the same time, or may be mixed in order. In the process of mixing each component, the temperature may be appropriately set, and thus heating and / or cooling may be performed temporarily or throughout. In addition, stirring or shaking may be performed in the process of mixing each component.
[0205] [14. Physical properties of resin composition] The cured product of the resin composition according to the first embodiment and the resin composition according to the second embodiment has excellent impact resistance. Therefore, the cured product of these resin compositions can form an insulating layer having excellent impact resistance. In detail, the insulating layer formed by the cured product of the above-mentioned resin composition can have excellent impact peel resistance and impact crack resistance.
[0206] Specifically, when an insulating layer is formed on a conductor layer using a cured product of a resin composition, the insulating layer can be prevented from peeling off from the conductor layer due to impact. In this case, for example, copper foil can be used as the conductor layer. The insulating layer can be formed by providing a resin composition layer containing a resin composition on the conductor layer and curing the resin composition. When the resin composition is thermosetting, the resin composition can be cured by heating under conditions of 180°C and 90 minutes. When the resin composition is photocurable, the resin composition can be cured under conditions of 1 J / cm. 2 This can be achieved by irradiating the film with ultraviolet light for 100 s, followed by heating at 180°C for 90 minutes.
[0207] In one example, a sample including a conductor layer and an insulating layer formed on the conductor layer by a cured product of a resin composition can suppress peeling of the insulating layer from the conductor layer when an impact is applied in a drop test described later. Specifically, when a drop test is performed on five samples, the number of samples in which peeling of the insulating layer from the conductor layer occurs can be reduced to preferably one or less, and more preferably to zero.
[0208] Furthermore, when an insulating layer is formed from a cured product of the resin composition, the insulating layer can suppress the formation of cracks and chips due to impact. In this case, the insulating layer can be formed by preparing a resin composition layer containing a resin composition and curing the resin composition. When the resin composition is thermosetting, the resin composition can be cured by heating under conditions of 180°C and 90 minutes. When the resin composition is photocurable, the resin composition can be cured by applying a current of 1 J / cm 2 This can be achieved by irradiating the film with ultraviolet light for 100 s, followed by heating at 180°C for 90 minutes.
[0209] In one example, a sample having an insulating layer formed from a cured product of a resin composition can suppress cracking and chipping of the insulating layer when an impact is applied in a drop test described later. Specifically, when a drop test is performed on five samples, the number of samples in which cracks or chips occur in the insulating layer can be reduced to preferably one or less, and more preferably to zero.
[0210] The drop test can be performed by the following method. FIG. 1 is a front view that shows a schematic view of a drop test performed for evaluating impact resistance. As shown in FIG. 1, a sample 11 is fixed to the bottom of a cylindrical weight 12 weighing 200 g using an adhesive tape (not shown) to prepare a test piece 13. The test piece 13 is allowed to freely drop three times from a height H of 1.5 m onto a steel disk 14 made of SS400, having a thickness of 20 mm and a diameter of 200 mm, with the sample 11 facing down. When the dropped test piece 13 collides with the steel disk 14, an impact is applied from the weight 12 to the sample 11. Thus, the impact resistance of the insulating layer included in the sample 11 can be evaluated by the drop test.
[0211] As a specific procedure for evaluating the impact resistance, the method described later in the Examples can be adopted.
[0212] The cured product of the resin composition according to the first embodiment and the resin composition according to the second embodiment can have a low relative dielectric constant. Therefore, the cured product of these resin compositions can form an insulating layer with a low relative dielectric constant. In one example, the relative dielectric constant of the cured product is preferably 3.1 or less, more preferably 3.0 or less, and particularly preferably 2.9 or less. There is no particular limit to the lower limit, and it can be, for example, 1.5 or more, 2.0 or more, etc.
[0213] The cured product of the resin composition according to the first embodiment and the resin composition according to the second embodiment can have a low dielectric loss tangent. Therefore, the cured product of these resin compositions can form an insulating layer with a low dielectric loss tangent. In one example, the dielectric loss tangent of the cured product is preferably 0.020 or less, more preferably 0.018 or less, and particularly preferably 0.016 or less. There is no particular limit to the lower limit, and it can be, for example, 0.001 or more, 0.002 or more, etc.
[0214] When the resin composition is heat-curable, the dielectric constant and the dielectric loss tangent can be measured, for example, using a cured product obtained by heat-curing the resin composition at 180°C for 90 minutes. When the resin composition is photocurable, the dielectric constant and the dielectric loss tangent can be measured, for example, using a cured product obtained by heat-curing the resin composition at 180°C for 90 minutes.2 After irradiating the cured product with ultraviolet light, the cured product is heated at 180° C. for 90 minutes to obtain a cured product. The dielectric constant and dielectric loss tangent of the cured product can be measured by a cavity resonance perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. The specific procedure for measuring the dielectric constant and dielectric loss tangent can be the same as that described in the Examples below.
[0215] The cured product of the resin composition according to the first embodiment and the resin composition according to the second embodiment can have a large breaking elongation. Therefore, the cured product of these resin compositions can form an insulating layer with a large breaking elongation. In one example, the breaking elongation of the cured product is preferably 0.5% or more, more preferably 1.0% or more, and particularly preferably 1.2% or more. There is no particular limit to the upper limit, and it can be, for example, 10% or less, 5.0% or less, etc.
[0216] When the resin composition is thermosetting, the breaking elongation can be measured using a cured product obtained by thermally curing the resin composition at 180° C. for 90 minutes. When the resin composition is photocurable, the breaking elongation can be measured using a cured product obtained by thermally curing the resin composition at 1 J / cm 2 After irradiating the film with ultraviolet light, the film is heated at 180°C for 90 minutes to obtain a cured product, which can be measured. The breaking elongation can be measured as the elongation percentage at the time of breakage by performing a tensile test at a temperature of 25°C (room temperature) and a tensile speed of 50 mm / min. The specific procedure for measuring the breaking elongation can be the same as that described in the Examples below.
[0217] [15. Uses of resin composition] The above-mentioned resin composition can be used as a resin composition for insulating purposes, and can be particularly preferably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer). For example, the above-mentioned resin composition can be used as a resin composition for forming an insulating layer of a printed wiring board, and can be preferably used as a resin composition for forming an interlayer insulating layer (resin composition for interlayer insulation).
[0218] The above-mentioned resin composition may be used as a resin composition for forming a rewiring formation layer (resin composition for forming a rewiring formation layer). The rewiring formation layer refers to an insulating layer for forming a rewiring layer. The rewiring layer refers to a conductor layer formed on the rewiring formation layer as an insulating layer. For example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the above-mentioned resin composition may be used as a resin composition for forming a rewiring formation layer. When a semiconductor chip package is manufactured through the following steps (1) to (6), a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0219] Furthermore, the above-mentioned resin composition can be used in a wide range of applications in which a resin composition is used, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulating material, a hole filling resin, and a component embedding resin.
[0220] [16. Sheet-type laminated materials] The above-mentioned resin composition may be used by coating in the form of a varnish, but from an industrial perspective, it is preferable to use the resin composition in the form of a sheet-like laminate material containing the resin composition.
[0221] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.
[0222] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support. The resin composition layer is formed of the above-mentioned resin composition. Thus, the resin composition layer usually includes a resin composition, and preferably includes only the resin composition.
[0223] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but may be 5 μm or more, 10 μm or more, etc.
[0224] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0225] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0226] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0227] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0228] As the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0229] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0230] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer.
[0231] The resin sheet can be produced, for example, by preparing a liquid (varnish-like) resin composition as is or by dissolving the resin composition in a solvent, applying this onto a support using a coating device such as a die coater, and then drying to form a resin composition layer.
[0232] The solvent may be the same as the solvent explained as a component of the resin composition. The solvent may be used alone or in combination of two or more.
[0233] Drying may be performed by heating, blowing hot air, or the like. Drying conditions are not particularly limited, but drying is performed so that the content of the solvent in the resin composition layer is usually 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the solvent in the resin composition, for example, when a resin composition containing 30% by mass to 60% by mass of a solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0234] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it is usually possible to use the resin sheet by peeling off the protective film.
[0235] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the above-mentioned resin composition.
[0236] The sheet-like fiber substrate used for the prepreg may be, for example, a commonly used substrate for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, and is usually 10 μm or more.
[0237] The prepreg can be produced by a method such as a hot melt method or a solvent method.
[0238] The thickness of the prepreg can be in the same range as that of the resin composition layer in the resin sheet described above.
[0239] The sheet-like laminate material can be suitably used for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be even more suitably used for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).
[0240] [17. Printed wiring boards] The printed wiring board according to one embodiment of the present invention includes an insulating layer containing a cured product obtained by curing the above-mentioned resin composition. This printed wiring board can be manufactured, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet on an inner layer substrate such that a resin composition layer of the resin sheet is bonded to the inner layer substrate. (II) A step of curing the resin composition layer to form an insulating layer.
[0241] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the above-mentioned "inner layer substrate". When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.
[0242] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.
[0243] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.
[0244] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.
[0245] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.
[0246] The support may be removed between step (I) and step (II) or after step (II).
[0247] In step (II), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition. The resin composition layer can be cured by a method suitable for the resin composition, such as thermal curing or photocuring. Specific curing conditions for the resin composition layer may be the conditions usually adopted when forming an insulating layer for a printed wiring board.
[0248] When a thermosetting resin composition is used, the curing of the resin composition may proceed as heat curing. Therefore, in this case, step (II) may include heat curing the resin composition layer. The heat curing conditions of the resin composition layer may vary depending on the type of resin composition. For example, the curing temperature is preferably 120°C to 240°C, more preferably 150°C to 220°C, and even more preferably 170°C to 210°C. The curing time may be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0249] In addition, when the resin composition layer is thermally cured, the method for producing a printed wiring board preferably includes preheating the resin composition layer at a temperature lower than the curing temperature before the thermal curing. For example, prior to thermal curing of the resin composition layer, the resin composition layer may be preheated at a temperature of usually 50° C. to 150° C., preferably 60° C. to 140° C., more preferably 70° C. to 130° C. for usually 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0250] On the other hand, when a photocurable resin composition is used, the curing of the resin composition may proceed as photocuring. In this case, therefore, step (II) may include photocuring the resin composition layer. The photocuring conditions of the resin composition may vary depending on the type of resin composition. For example, the resin composition layer in the irradiated area may be photocured by exposure treatment in which the resin composition layer is irradiated with actinic rays. Examples of actinic rays include ultraviolet rays, visible rays, electron beams, X-rays, etc., and ultraviolet rays are particularly preferred. The irradiation dose of ultraviolet rays is, for example, 10 mJ / cm. 2 ~1000mJ / cm 2 When a resin sheet having a support is used, exposure may be performed through the support, or after the support is peeled off.
[0251] In the exposure treatment, the resin composition layer may be irradiated with active light through a mask having a pattern formed thereon. Exposure methods using a mask include a contact exposure method in which exposure is performed by contacting a mask with a workpiece, and a non-contact exposure method in which exposure is performed using parallel light without contact, and either method may be used.
[0252] Step (II) may include carrying out a development treatment after the exposure treatment. According to the development treatment, the part not photocured (unexposed part) can be removed to form a pattern in the cured body layer. The development is usually carried out by wet development. In the wet development, a developer that is safe, stable, and easy to operate, such as an alkaline aqueous solution, a water-based developer, or an organic solvent, is used. Among them, a development step using an alkaline aqueous solution is preferred. As the development method, for example, a method such as spraying, swing immersion, brushing, or scraping can be adopted.
[0253] Furthermore, in the case where the resin composition layer is photocured, a post-baking treatment may be carried out as necessary after photocuring and development. Examples of the post-baking treatment include ultraviolet irradiation treatment using a high-pressure mercury lamp and heating treatment using a clean oven. The ultraviolet irradiation treatment is carried out at a dose of, for example, 0.05 J / cm. 2 ~10J / cm 2 The heat treatment can be carried out, for example, at a temperature of preferably 150° C. to 250° C. for 20 minutes to 180 minutes, and more preferably at a temperature of 160° C. to 230° C. for 30 minutes to 120 minutes.
[0254] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art that are used in manufacturing printed wiring boards. When the support is removed after step (II), the removal of the support may be carried out between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer in steps (I) to (V) may be repeated to form a multilayer wiring board, as necessary.
[0255] In another embodiment, the printed wiring board can be manufactured using the above-mentioned prepreg. The manufacturing method can be basically the same as when a resin sheet is used.
[0256] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole may be appropriately determined depending on the design of the printed wiring board.
[0257] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0258] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using a swelling liquid can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.
[0259] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0260] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.
[0261] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.
[0262] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0263] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.
[0264] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method. From the viewpoint of ease of production, the semi-additive method is preferred. Below, an example of forming the conductor layer by the semi-additive method is shown.
[0265] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.
[0266] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.
[0267] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0268] [18. Semiconductor Devices] A semiconductor device according to an embodiment of the present invention includes the above-mentioned printed wiring board. The semiconductor device can be manufactured using the printed wiring board.
[0269] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES
[0270] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to these examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. In addition, the temperature and pressure conditions were room temperature (25°C) and atmospheric pressure (1 atm), unless otherwise specified.
[0271] [Synthesis Example 1: Synthesis of Resin (a1) Containing an Ethylenically Unsaturated Bond and a Carboxyl Group] A naphthol aralkyl type epoxy resin represented by the following formula (1) ("ESN-475V" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., epoxy equivalent: approximately 325 g / eq.) was prepared.
[0272] [ka]
[0273] In the formula (1), Z is a glycidyl group (Gl) or a hydrocarbon group (R6) having 1 to 8 carbon atoms, and the ratio of R6 / Gl is 0.05 to 2.0. Also, n is a number ranging from 1 to 6 as an average value.
[0274] 325 parts of this naphthol aralkyl type epoxy resin ("ESN-475V" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., epoxy equivalent of about 325g / eq.) was placed in a flask equipped with a gas inlet tube, a stirrer, a cooling tube and a thermometer, 340 parts of carbitol acetate was added, heated and dissolved, and 0.46 parts of hydroquinone and 1 part of triphenylphosphine were added. This mixture was heated to 95°C to 105°C, 72 parts of acrylic acid were gradually added dropwise, and reacted for 16 hours. This reaction product was cooled to 80°C to 90°C, 80 parts of tetrahydrophthalic anhydride were added, reacted for 8 hours, and cooled. In this way, a resin solution with an acid value of 60mgKOH / g of solid matter (non-volatile content 70%, hereinafter sometimes abbreviated as "resin (a1) solution") was obtained. It was confirmed that this resin (a1) solution contains at least resin (a1) having a structure shown in the following formula (2).
[0275] [ka]
[0276] [Example 1] 10 parts of bisphenol A type epoxy resin ("828EL" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent weight approximately 180 g / eq.) and 25 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent weight approximately 269 g / eq.) were added with 50 parts of methyl ethyl ketone, and dissolved by heating with stirring. This was cooled to room temperature to prepare an epoxy resin dissolved composition. To this epoxy resin solution, 10 parts of a triazine skeleton-containing phenolic curing agent (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%), 10 parts of a naphthol-type curing agent (Nippon Steel Chemical & Material Co., Ltd.'s "SN-485", hydroxyl group equivalent of about 205 g / eq.), 15 parts of a phenoxy resin (Mitsubishi Chemical Corporation's "YX7553BH30", a 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass), and spherical silica (Admatechs Corporation's "SO-C2", average particle size 0.5 μm, BET specific surface area 5.8 m) as a solid inorganic filler that had been surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573"). 2 50 parts of hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) 2 A resin varnish was prepared by mixing 25 parts of 1000g / g, porosity 50% by volume, 3 parts of rubber particles ("PARALOID EXL2655" manufactured by Dow Chemical Japan; core-shell particles with a core formed of a polymer of butadiene (specific gravity 0.91) and a shell formed of a copolymer of styrene (specific gravity 1.06) and methyl methacrylate (specific gravity 1.18); average particle size 0.2 μm) and 4 parts of an amine-based curing accelerator (4-dimethylaminopyridine (DMAP), MEK solution with a solid content of 5% by mass) and dispersing the mixture uniformly in a high-speed rotating mixer. The inorganic filler contained in this resin varnish has an average particle size of 1.1 μm and a BET specific surface area of 9.0 m 2 / g.
[0277] Next, the resin varnish was uniformly applied onto the release surface of the support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin was dried at 80°C to 120°C (average 100°C) for 5 minutes to produce a resin sheet.
[0278] [Example 2] Spherical silica (Admatechs' "SO-C2") surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was not used. In addition, hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m 2 The amount of 0.1% by volume porosity was changed from 25 parts to 50 parts. Furthermore, 3 parts of biphenylaralkylnovolac-type maleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., a MEK / toluene mixed solution with a non-volatile content of 70%) was added to the resin varnish. Except for the above, a resin varnish and a resin sheet were produced in the same manner as in Example 1. The average particle size of the inorganic filler contained in the resin varnish was 1.6 μm, and the BET specific surface area was 12 m. 2 / g.
[0279] [Example 3] Spherical silica (Admatechs' "SO-C2") surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was not used. In addition, hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m 2 Instead of 25 parts of SiO2 / g and porosity of 50% by volume, hollow silica particles 2 (average particle size 2.0 μm, BET specific surface area 3.8 m2) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) were used. 2 80 parts of 1000g / g and porosity 20% by volume were used. Furthermore, instead of 3 parts of rubber particles ("PARALOID EXL2655" manufactured by Dow Chemical Japan), 3 parts of hollow acrylic particles ("XX-5598Z" manufactured by Sekisui Chemical Co., Ltd.; hollow particles having a shell portion formed from a copolymer of styrene (specific gravity 1.06) and methyl methacrylate (specific gravity 1.18) and a hollow portion formed within the shell portion; average particle size 0.5 μm, porosity 35% by volume) were used. Further, 5 parts of vinylbenzyl-modified polyphenylene ether ("OPE-2St 2200" manufactured by Mitsubishi Gas Chemical Co., Ltd., a toluene solution with a non-volatile content of 65%) was added to the resin varnish. Except for the above, a resin varnish and a resin sheet were produced in the same manner as in Example 1. The average particle size of the inorganic filler contained in the resin varnish was 2.0 μm, and the BET specific surface area was 3.8 m. 2 / g.
[0280] [Example 4] Instead of 25 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd.), 25 parts of naphthylene ether type epoxy resin (epoxy equivalent: about 250 g / eq., "HP6000" manufactured by DIC Corporation) was used. In addition, hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m 2 Instead of 25 parts of the glass, hollow alumina borosilicate glass particles (manufactured by Taiheiyo Cement Corporation, "MG-005", average particle size 1.6 μm, BET specific surface area 6.5 m) surface-treated with a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-573") were used. 2 22 parts of 1000g / g, porosity 80% by volume) were used. In addition, the amount of rubber particles (PARALOID EXL2655, manufactured by Dow Chemical Japan) was changed from 3 parts to 5 parts. Except for the above, a resin varnish and a resin sheet were produced in the same manner as in Example 1. The average particle size of the inorganic filler contained in the resin varnish was 1.1 μm, and the BET specific surface area was 6.2 m. 2 / g.
[0281] [Example 5] Five parts of rubber particles (Dow Chemical Japan's "PARALOID EXL2655") were replaced with five parts of rubber particles (Aica Kogyo's "Staphyloid AC3816N"; core-shell particles with a core formed from a polymer of butyl acrylate (specific gravity 1.09) and a shell formed from a polymer of methyl methacrylate (specific gravity 1.18); average particle size 0.5 μm). Except for the above, a resin varnish and a resin sheet were produced in the same manner as in Example 4. The average particle size of the inorganic filler contained in the resin varnish was 1.1 μm, and the BET specific surface area was 6.2 m. 2 / g.
[0282] [Example 6] 50 parts of methyl ethyl ketone was added to 10 parts of naphthalene type epoxy resin (DIC "HP-4032-SS", epoxy equivalent: approx. 144 g / eq.), and the mixture was heated with stirring to homogenize. The mixture was then cooled to room temperature to prepare an epoxy resin dissolved composition. To this epoxy resin solution, 30 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 2 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%), 5 parts of a carbodiimide hardener (Nisshinbo Chemical Co., Ltd.'s "V-03", active group equivalent of about 216 g / eq., toluene solution with non-volatile content of 50%), and hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573") were added. 2 A resin varnish was prepared by mixing 45 parts of 100% cellulose acetate (1.0 g / g, porosity 50% by volume), 5 parts of rubber particles (Dow Chemical Japan's "PARALOID EXL2655"), and 0.1 parts of an imidazole-based curing accelerator (Shikoku Chemical Industry Co., Ltd.'s "1B2PZ", 1-benzyl-2-phenylimidazole), and dispersing the mixture uniformly in a high-speed rotating mixer. The inorganic filler contained in the resin varnish has an average particle size of 1.6 μm and a BET specific surface area of 12 m 2 / g.
[0283] Next, the resin varnish was uniformly applied onto the release surface of the support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin was dried at 80°C to 120°C (average 100°C) for 5 minutes to produce a resin sheet.
[0284] [Example 7] To 10 parts of naphthalene type epoxy resin (DIC Corporation "HP-4032-SS", epoxy equivalent approximately 144 g / eq.), 10 parts of bisphenol A type epoxy resin (Mitsubishi Chemical Corporation "828EL", epoxy equivalent approximately 180 g / eq.), 15 parts of naphthylene ether type epoxy resin (DIC Corporation "HP6000", epoxy equivalent approximately 250 g / eq.), and 50 parts of methyl ethyl ketone were added and heated to dissolve with stirring. This was cooled to room temperature to prepare an epoxy resin dissolved composition. To this epoxy resin solution, 15 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%), 20 parts of a prepolymer of bisphenol A dicyanate (Lonza Japan's "BA230S75", cyanate equivalent of about 232 g / eq., MEK solution with non-volatile content of 75% by mass), and spherical silica (Admatechs' "SO-C2", BET specific surface area of 5.8 m) as a solid inorganic filler that had been surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd.'s "KBM-573"). 2 / g, average particle size 0.5 μm), 60 parts of hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.). 230 parts of cellulose acetate (1.0 g, porosity 50 vol%), 5 parts of rubber particles (Dow Chemical Japan "PARALOID EXL2655"), 4 parts of amine-based curing accelerator (4-dimethylaminopyridine (DMAP), MEK solution with 5 mass% solids), 1 part of MEK solution with 1 mass% cobalt (III) acetylacetonate (Tokyo Chemical Industry Co., Ltd.), and 8 parts of phenoxy resin (Mitsubishi Chemical Corporation "YX7553BH30", 1:1 solution of MEK and cyclohexanone with 30 mass% non-volatiles) were mixed and uniformly dispersed in a high-speed rotating mixer to prepare a resin varnish. The average particle size of the inorganic filler contained in the resin varnish is 1.1 μm, and the BET specific surface area is 9.0 m 2 / g.
[0285] Next, the resin varnish was uniformly applied onto the release surface of the support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin was dried at 80°C to 120°C (average 100°C) for 5 minutes to produce a resin sheet.
[0286] [Example 8] 5 parts of naphthalene type epoxy resin (DIC "HP-4032-SS", epoxy equivalent: about 144) were added to 10 parts of biphenyl type epoxy resin (Nippon Kayaku "NC3000L", epoxy equivalent: about 269 g / eq.), 7 parts of biphenyl aralkyl novolac type maleimide (Nippon Kayaku "MIR-3000-70MT", MEK / toluene mixed solution with non-volatile content of 70%), 10 parts of methyl ethyl ketone, and 10 parts of diethylene glycol monoethyl ether acetate, and the mixture was heated and dissolved while stirring. The mixture was cooled to room temperature to prepare an epoxy resin solution. The epoxy resin solution was mixed with spherical silica (Admatechs "SO-C2", BET specific surface area: 5.8 m) as a solid inorganic filler surface-treated with a silane coupling agent (Shin-Etsu Chemical "KBM-573"). 256 parts of hollow silica particles 1 (average particle size 0.5 μm), 28 parts of hollow silica particles 1 surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.), 0.02 parts of an imidazole-based curing accelerator ("1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd., 1-benzyl-2-phenylimidazole), and 5 parts of rubber particles ("PARALOID EXL2655" manufactured by Dow Chemical Japan) were mixed and uniformly dispersed in a high-speed rotating mixer. Next, 50 parts of the resin (a1) solution produced in Synthesis Example 1 and 5 parts of a photopolymerization initiator ("IrgacureTPO" manufactured by BASF, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide) were added and stirred at room temperature until uniform, to prepare a resin varnish. The inorganic filler contained in the resin varnish has an average particle size of 1.1 μm and a BET specific surface area of 9.0 m 2 / g.
[0287] Next, the resin varnish was uniformly applied onto the release surface of the support, a release-treated polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm), so that the thickness of the resin composition layer was 40 μm, and the resin was dried at 80°C to 120°C (average 100°C) for 5 minutes to produce a resin sheet.
[0288] [Comparative Example 1] The amount of spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm) surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was changed from 50 parts to 100 parts. In addition, hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m 2 / g, porosity 50% by volume was not used. In addition, the amount of rubber particles (PARALOID EXL2655, manufactured by Dow Chemical Japan) was changed from 3 parts to 5 parts. A resin varnish and a resin sheet were produced in the same manner as in Example 1 except for the above.
[0289] [Comparative Example 2] Spherical silica (Admatechs' SO-C2, average particle size 0.5 μm) surface-treated with a silane coupling agent (Shin-Etsu Chemical's KBM-573) and rubber particles (Dow Chemical Japan's PARALOID EXL2655) were not used. In addition, hollow silica particles 1 (average particle size 1.6 μm, BET specific surface area 12 m 2 Instead of 25 parts of SiO2 / g and porosity of 50% by volume, hollow silica particles 2 (average particle size 2.0 μm, BET specific surface area 3.8 m2) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) were used. 2 80 parts of 1000g / g and porosity 20% by volume were used. A resin varnish and a resin sheet were produced in the same manner as in Example 1 except for the above.
[0290] [Measurement of dielectric tangent] (1-1) Preparation of Cured Products for Evaluation (Examples 1 to 7, Comparative Examples 1 and 2): A PET film ("501010" manufactured by Lintec Corporation, thickness 50 μm, 240 mm square) having a surface treated with a release agent (release agent-treated surface) and a surface not treated with a release agent (release agent-untreated surface) was prepared. A glass cloth-based epoxy resin double-sided copper-clad laminate ("R5715ES" manufactured by Panasonic Corporation, thickness 0.7 mm, 255 mm square) was placed on the release agent-untreated surface of this PET film, and the four sides were fixed with polyimide adhesive tape (width 10 mm). The PET film thus fixed to the glass cloth-based epoxy resin double-sided copper-clad laminate may be referred to as "fixed PET film" below.
[0291] The resin varnishes prepared in Examples 1 to 7 and Comparative Examples 1 and 2 were applied to the release-treated surface of a fixed PET film using a die coater so that the thickness of the resin composition layer after drying was 40 μm, and the film was dried at 80° C. to 120° C. (average 100° C.) for 10 minutes to form a resin composition layer. The film was then placed in an oven at 180° C. and heated for 90 minutes to heat-cure the resin composition layer. After heat-cure, the polyimide adhesive tape was peeled off, the glass cloth-based epoxy resin double-sided copper-clad laminate was removed, and the PET film ("501010" manufactured by Lintec Corporation) was also peeled off to obtain a sheet-shaped cured product. The obtained cured product may be referred to as a "cured product for evaluation."
[0292] (1-2) Preparation of Cured Product for Evaluation (Example 8): The resin varnish prepared in Example 8 was applied to the release-treated surface of the fixed PET film using a die coater so that the thickness of the resin composition layer after drying would be 40 μm, and the film was dried at 80° C. to 120° C. (average 100° C.) for 10 minutes to form a resin composition layer. 2 After irradiating with ultraviolet light, the resin composition layer was cured by heating in an oven at 180°C for 90 minutes. After curing, the polyimide adhesive tape was peeled off, the glass cloth-based epoxy resin double-sided copper-clad laminate was removed, and the PET film ("501010" manufactured by Lintec Corporation) was also peeled off to obtain a sheet-like cured product. The obtained cured product is referred to as "cured product for evaluation".
[0293] (2) Measurement of relative dielectric constant and dielectric loss tangent: The cured product for evaluation was cut into a length of 80 mm and a width of 2 mm to obtain an evaluation sample. The relative dielectric constant and dielectric loss tangent of this evaluation sample were measured at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C by a cavity resonance perturbation method using an Agilent Technologies HP8362B device. Measurements were performed on two test pieces, and the average value was calculated.
[0294] [Evaluation of the linear thermal expansion coefficient of the cured product] The cured product for evaluation was cut into a length of about 15 mm and a width of about 5 mm to obtain a test piece. A thermomechanical analysis of the test piece was performed by the tensile load method using a thermomechanical analyzer (Rigaku Corporation's "Thermo Plus TMA8310"). Specifically, after mounting the test piece on the device, measurements were performed twice in succession under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. In the second measurement, the glass transition temperature and the average linear thermal expansion coefficient (thermal expansion coefficient) in the temperature range from 25°C to 150°C were calculated.
[0295] [Measurement of specific gravity of hardened product] The cured product for evaluation was cut into a length of approximately 3 cm and a width of approximately 3 cm to obtain a test piece. The specific gravity of the test piece was measured using a Mettler Toledo analytical balance "XP105" (using a specific gravity measurement kit). Measurements were performed on five test pieces, and the average value was calculated.
[0296] [Measurement of breaking elongation of cured product] The cured products for evaluation were subjected to a tensile test in accordance with Japanese Industrial Standards (JIS K7161) at a temperature of 25°C (room temperature) and a tensile speed of 50 mm / min using a Tensilon universal testing machine (manufactured by A&D Co., Ltd.), and the elongation at the time of break (breaking elongation) was measured.
[0297] [Evaluation of impact peel resistance and impact crack resistance] (1) Preparation of inner layer board: Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") were etched 1 μm with a microetching agent (Mec "CZ8101") to roughen the copper surface, and an inner layer substrate was obtained.
[0298] (2) Lamination of resin sheet: Using a batch-type vacuum pressure laminator (two-stage build-up laminator "CVP700" manufactured by Nikko Materials Co., Ltd.), the resin sheets obtained in the examples and comparative examples were laminated on both sides of the inner layer substrate so that the resin composition layer was in contact with the inner layer substrate. The lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Next, a heat press was performed at 100°C and a pressure of 0.5 MPa for 60 seconds to obtain an intermediate substrate having a layer structure of support / resin composition layer / inner layer substrate / resin composition layer / support.
[0299] (3-1) Curing of Resin Composition Layer (Examples 1 to 7, Comparative Examples 1 and 2): The resin composition layer was cured under heat curing conditions of 180° C. for 90 minutes to form an insulating layer, after which the support was peeled off to obtain an evaluation substrate having a layer structure of insulating layer / inner layer substrate / insulating layer.
[0300] (3-2) Curing of Resin Composition Layer (Example 8): 1 J / cm2 on the resin composition layer 2 The resin composition layer was cured by heating at 180° C. for 90 minutes to form an insulating layer. The support was then peeled off to obtain a substrate for evaluation having a layer structure of insulating layer / inner layer substrate / insulating layer.
[0301] (4) Drop test: The evaluation substrate was cut to 10 mm x 10 mm to obtain a plurality of substrate pieces. As shown in Fig. 1, the substrate pieces as sample 11 were fixed to the bottom of a cylindrical weight 12 weighing 200 g using adhesive tape (not shown) to prepare five test pieces 13. Each test piece 13 was allowed to freely drop three times from a height H of 1.5 m onto a steel disk 14 made of SS400, 20 mm thick and 200 mm in diameter, with the substrate piece as sample 11 facing down.
[0302] (5) Evaluation of impact peel resistance: The substrate pieces after the drop test were observed, and the impact peel resistance of the substrate pieces was judged according to the following criteria. Excellent impact peel resistance means that the insulating layer is unlikely to peel even when subjected to an impact caused by a drop. Therefore, excellent impact peel resistance means that the insulating layer has high resistance to peeling caused by an impact. "Excellent": No peeling was observed in any of the five substrate pieces after the drop test. "Fair": Peeling was observed in only one sample out of five substrate pieces after the drop test. "Fail": Peeling was observed in two or more samples out of five board pieces after the drop test.
[0303] (6) Impact crack resistance evaluation: The substrate pieces after the drop test were observed, and the impact crack resistance of the substrate pieces was judged according to the following criteria. Excellent impact crack resistance means that cracks are unlikely to occur in the insulating layer even when subjected to an impact from a drop. Thus, excellent impact crack resistance means that the insulating layer has high resistance to cracks caused by an impact. "Excellent": None of the five board pieces were found to have any cracks or chips after the drop test. "Acceptable": After the drop test, only one of the five substrate samples showed cracks or chips. "Fail": Of the five board pieces after the drop test, two or more samples showed cracks or chips.
[0304] [result] The compositions and evaluation results of the resin compositions in the examples and comparative examples are shown in the following table. In the "impact peel resistance" column of Table 3, the numerical values shown together with the evaluation results indicate the number of pieces that peeled off out of the five substrate pieces. In the "impact crack resistance" column of Table 3, the numerical values shown together with the evaluation results indicate the number of pieces that cracked or chipped out out of the five substrate pieces. In the table below, the abbreviations have the following meanings: a1: Resin (a1) produced in Synthesis Example 1. Hollow glass particles: hollow alumina borosilicate glass particles.
[0305] [Table 1]
[0306] [Table 2]
[0307] [Table 3] [Explanation of symbols]
[0308] 11 Sample 12 weight 13 Test specimen 14 Steel disc
Claims
1. A resin composition comprising (A) a curable resin, (B) an inorganic filler, and (C) organic particles, (A) the curable resin includes an epoxy resin; (B) The inorganic filler contains (B-1) a hollow inorganic filler having pores therein; The amount of the inorganic filler (B) is 40% by volume or more relative to 100% by volume of the nonvolatile components of the resin composition; (B) the average particle size of the inorganic filler is 0.01 μm or more and 3 μm or less; The specific gravity of the cured product obtained by curing the resin composition is 1.6 g / cm 3 is as follows: A resin composition, wherein a cured product obtained by curing the resin composition has a thermal expansion coefficient of 25 ppm / °C or less, as measured by thermomechanical analysis using a tensile load method under measurement conditions of a load of 1 g, a heating rate of 5°C / min in the temperature range of 25°C to 150°C.
2. (B) The BET specific surface area of the inorganic filler is 1 m 2 / g or more, 100m 2 The resin composition according to claim 1, wherein the viscosity is 100 / g or less.
3. The resin composition according to claim 1, wherein the hollow inorganic filler (B-1) has a porosity of 10 volume% or more.
4. The resin composition according to claim 1, wherein the amount of the organic particles (C) is 2% by mass or more based on 100% by mass of the nonvolatile components of the resin composition.
5. The resin composition according to claim 1, wherein the organic particle (C) has a shell portion and a built-in portion formed within the shell portion, and the built-in portion contains a rubber component or is a hollow portion.
6. 2. The resin composition according to claim 1, wherein the curable resin (A) is selected from the group consisting of thermosetting resins and photocurable resins.
7. The resin composition according to claim 6, wherein the thermosetting resin comprises at least one resin selected from the group consisting of a phenolic resin, an active ester resin, a cyanate resin, and a radical polymerizable resin.
8. The resin composition according to claim 6 , wherein the photocurable resin comprises a radically polymerizable resin.
9. The resin composition according to claim 1 , which is for forming an insulating layer.
10. A cured product of the resin composition according to any one of claims 1 to 9.
11. A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 9.
12. A resin sheet comprising a support and a resin composition layer formed on the support from the resin composition according to any one of claims 1 to 9.
13. A printed wiring board comprising an insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 9.
14. A semiconductor device comprising the printed wiring board according to claim 13.
Citation Information
Patent Citations
Epoxy adhesive
JP2019011445A
Epoxy resin composition for collectively sealing, electronic device and method for manufacturing the same
JP2019026715A
Resin composition
JP2020083966A
Photosensitive resin composition
JP2020154326A
resin composition
JP2022027768A